Fiber-reinforced polypropylene composition

By using heterophase polypropylene composition (HECO) in fiber-reinforced polypropylene materials, combining fibers and binders, optimizing the material composition and structure, the problem of insufficient mechanical properties of existing materials at high filling rates is solved, and the effects of high tensile modulus and elongation at break are achieved.

JP7654801B2Active Publication Date: 2025-04-01BOREALIS AG
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023541565
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-01-27
Filing Date
2022-01-20
Publication Date
2025-04-01
Estimated Expiration
2042-01-20

Smart Images

  • Figure 0007654801000011
    Figure 0007654801000011
  • Figure 0007654801000001
    Figure 0007654801000001
  • Figure 0007654801000002
    Figure 0007654801000002
Patent Text Reader

Abstract

The present invention is directed to a fiber reinforced composition (C) comprising a heterophasic polypropylene composition (HECO), a fiber (F) and an adhesion promoter (AP), and to an article comprising said fiber reinforced composition (C).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention is directed to a fiber reinforced composition (C) comprising a heterophasic polypropylene composition (HECO), a fiber (F) and an adhesion promoter (AP), and to an article comprising said fiber reinforced composition (C). [Background technology]

[0002] Fiber-reinforced materials are widely used in various applications, especially in engineering fields where higher stiffness and good impact resistance are seen as benefits. Polypropylene is one of the most popular base polymers due to its versatility, low cost and low density. It can meet most of the target properties. Polypropylene prepared in the presence of metallocene catalysts is a promising candidate due to additional advantages such as controlled molecular weight distribution, good comonomer incorporation and low emissions. However, due to the nature of the compound, tensile strength and elongation at break are often compromised at high loadings.

[0003] Therefore, there is a need in the art for a fiber reinforced polypropylene composition that is characterized by excellent heat distortion properties and low emissions, while maintaining high levels of tensile strength and elongation at break. Summary of the Invention [Problem to be solved by the invention]

[0004] It is therefore an object of the present invention to provide a fiber reinforced polypropylene composition having good mechanical properties, preferably based on polypropylene prepared in the presence of a metallocene catalyst. [Means for solving the problem]

[0005] Thus, the present invention relates to a fiber-reinforced composition (C), based on the total weight of the fiber-reinforced composition (C), a) 55.0 to 95.0 wt. % of a heterophasic polypropylene composition (HECO), i) a matrix that is a homopolymer or copolymer of propylene (PP) having 1,2 erythro regio-defects in an amount of at least 0.4 mole percent (mol-%) and a comonomer content of 8.5 mol-% or less; and ii) an elastomeric ethylene copolymer (E) dispersed in the matrix; a heterophasic polypropylene composition (HECO) comprising: b) 5.0 to 45.0% by weight of fiber (F); c) optionally 0.1 to 5.0 wt. % of an adhesion promoter (AP); Including, The fiber-reinforced composition (C) is directed to a fiber-reinforced composition (C) having a melt flow rate MFR2 (230°C, 2.16 kg) determined in accordance with ISO 1133 in the range of 1.0 to 60.0 g / 10 min.

[0006] According to one embodiment of the present invention, the heterophasic polypropylene composition (HECO) comprises, based on the total weight of the heterophasic copolymer (HECO), i) the matrix being 60.0 to 95.0% by weight of a propylene homopolymer or copolymer (PP), and ii) 5.0 to 40.0 wt. % of an elastomeric ethylene copolymer (E) Includes.

[0007] According to a further embodiment of the present invention, the elastomeric ethylene copolymer (E) has an ethylene content in the range of 15.0 to 85.0 wt.%, based on the total weight of the elastomeric ethylene copolymer (E).

[0008] According to another embodiment of the present invention, the heterophasic polypropylene composition (HECO) has a melting temperature Tm determined according to differential scanning calorimetry (DSC) in the range of 130-165°C.

[0009] According to one embodiment of the present invention, the heterophasic polypropylene composition (HECO) has an intrinsic viscosity (IV) measured according to ISO 1628 / 1 (135° C. in decalin) of the soluble part (soluble fraction, SF) determined according to CRYSTEX QC in the range of 1.8 to 3.0 dl / g.

[0010] According to a further embodiment of the invention, the fibers (F) are glass fibers (GF), preferably i) an average length of 2.0 to 10.0 mm, and / or ii) average diameter between 5 and 20 μm The fiber is short glass fiber (SGF) having the above structure.

[0011] According to another embodiment of the invention, the adhesion promoter (AP) is a polar modified polypropylene (PM-PP), which is a homopolymer or copolymer of propylene grafted with maleic anhydride, having a melt flow rate MFR2 (230°C, 2.16 kg) determined according to ISO 1133 of at least 20.0 g / 10 min.

[0012] According to a first embodiment of the invention, the homopolymer or copolymer of propylene (PP) is a propylene homopolymer (hPP) and the elastomeric ethylene polymer (E) is a copolymer of ethylene and propylene.

[0013] According to a first embodiment of the invention, the propylene homopolymer (hPP) has a melting temperature Tm, determined according to differential scanning calorimetry (DSC), in the range of 140-160°C.

[0014] According to a first embodiment of the present invention, the heterophasic polypropylene composition (HECO) has a comonomer content in the range of 2.2-8.7 mol %.

[0015] The heterophasic polypropylene composition (HECO) according to the first embodiment of the present invention is i) a xylene cold solubles (XCS) content, determined at 25°C according to ISO 16152, in the range of 5.0 to 35.0% by weight based on the total weight of the heterophasic polypropylene composition (HECO); and / or ii) an ethylene content of the xylene cold solubles (XCS) fraction in the range of 20.9 to 44.7 mole percent; and / or ii) a soluble fraction (SF) determined according to CRYSTEX QC in the range of 5.0 to 35.0 wt. % based on the total weight of the heterophasic polypropylene composition (HECO), and / or iv) Ethylene content of the soluble fraction (SF) determined according to CRYSTEX QC in the range of 20.9-44.7 mol% It is particularly preferred that

[0016] According to a first embodiment of the present invention, the heterophasic polypropylene composition (HECO) has a melt flow rate MFR2 (230°C, 2.16 kg) determined according to ISO 1133 in the range of 20.0 to 100 g / 10 min.

[0017] According to a first embodiment of the invention, the fiber-reinforced composition (C) has a tensile modulus, determined according to ISO 527-1A, in the range of 3000 to 6000 MPa and / or an elongation at break, determined according to ISO 527-2, of more than 3.0%.

[0018] According to a second embodiment of the present invention, the propylene homopolymer or copolymer (PP) is preferably a propylene copolymer (cPP) of propylene and ethylene having an ethylene content of 2.2 to 8.5 mol %, and the elastomeric ethylene copolymer (E) is preferably a copolymer of ethylene and a C4-C propylene copolymer (CPP) having an ethylene content of 55.0 to 85.0 wt %, based on the total weight of the elastomeric ethylene copolymer (E). 12 It is a copolymer with an α-olefin, preferably 1-octene.

[0019] According to a second embodiment of the invention, the propylene copolymer (cPP) has a melt flow rate MFR2 (230 °C, 2.16 kg) determined according to ISO 1133 in the range of 5.0 to 20.0 g / 10 min and / or the elastomeric ethylene copolymer (E) has a melt flow rate MFR (190 °C, 2.16 kg) determined according to ISO 1133 in the range of 0.8 to 20.0 g / 10 min and / or a melt flow rate MFR (190 °C, 2.16 kg) determined according to ISO 1133 in the range of 860 to 890 kg / m 3 having a density determined in accordance with ISO 1183-187 in the range of

[0020] According to a second embodiment of the present invention, the fiber reinforced composition (C) has a melt flow rate MFR2 (230° C., 2.16 kg) determined according to ISO 1133 in the range of 1.0 to 10.0 g / 10 min.

[0021] According to a second embodiment of the invention, the fiber-reinforced composition (C) has a tensile modulus, determined according to ISO 527-1A, in the range of 2500 to 5500 MPa and / or an elongation at break, determined according to ISO 527-2, of more than 10.0%.

[0022] According to one embodiment of the present invention, the fiber-reinforced composition (C) is 20.0% by weight or less of 900 kg / m 3 Further included are low density polyethylene (LDPE) homopolymers or copolymers having a density, determined in accordance with ISO 1183-187, of greater than 100% and comprising ethylene and optionally vinyl acetate.

[0023] According to one embodiment of the invention, a propylene homo- or copolymer (PP) is obtained in the presence of a solid catalyst system (SCS) comprising a metallocene compound, which metallocene compound has particularly preferably the formula (I): [ka] In the above formula (I), each X is independently a σ-donor ligand; L is a divalent bridge group selected from -R'2C-, -R'2C-CR'2-, -R'2Si-, -R'2Si-SiR'2-, -R'2Ge-, and each R' is independently a hydrogen atom or a C1-C aryl group optionally containing one or more heteroatoms or fluorine atoms from groups 14 to 16 of the periodic table. 20 - a hydrocarbyl group, or optionally two R' groups can be taken together to form a ring; Each R 1 can be independently the same or different and are hydrogen, a linear or branched C1-C6 alkyl group, C 7~20 -aryl alkyl, C 7~20 -alkylaryl group or C 6~20 -aryl group or OY group, Y is C 1~10 -hydrocarbyl group, optionally with two adjacent R 1 The groups can be part of a ring that includes the phenyl carbon to which they are attached; Each R 2 can be independently the same or different, and CH-R 8 is a group, R 8 is H or a linear or branched C 1~6 -Alkyl group, C 3~8 -Cycloalkyl group, C 6~10 -aryl group, R 3 is a linear or branched C1-C6 alkyl group, C 7~20 -aryl alkyl, C 7~20 -Alkylaryl group or C6-C 20 -aryl group, R 4 is C(R 9 ) 3 groups, R 9 is a linear or branched C1-C6 alkyl group, R 5 is hydrogen or an aliphatic C1-C which may contain one or more heteroatoms from groups 14 to 16 of the periodic table; 20 - a hydrocarbyl group, R 6is hydrogen or an aliphatic C1-C which may contain one or more heteroatoms from groups 14 to 16 of the periodic table; 20 - a hydrocarbyl group, or R 5 and R 6 together form n groups R 10 wherein n is 0 to 4, Each R 10 are the same or different, C1 to C 20 - a hydrocarbyl group or a C1-C group which may contain one or more heteroatoms belonging to groups 14 to 16 of the periodic table 20 -hydrocarbyl group, R 7 is H or a linear or branched C1-C6-alkyl group or 1-3 groups R 11 is an aryl or heteroaryl group having 6 to 20 carbon atoms, optionally substituted by Each R 11 can be independently the same or different and are hydrogen, a linear or branched C1-C6 alkyl group, C 7~20 -aryl alkyl, C 7~20 -alkylaryl group or C 6~20 -aryl group or OY group, Y is C 1~10 -hydrocarbyl groups.

[0024] The present invention is further directed to an article comprising the above-described fiber-reinforced composition (C). [Brief description of the drawings]

[0025] [Figure 1] (a): Schematic of the CRYSTEX QC instrument. (b): Elution of the EP copolymer sample and the resulting soluble and crystalline fractions on a TREF column.

[0026] The fiber-reinforced composition (C) will be described in more detail below.

[0027] Fiber-reinforced composition (C) The present invention is directed to a fiber reinforced composition (C) comprising a heterophasic polypropylene composition (HECO), a fiber (F) and an adhesion promoter (AP).

[0028] In particular, the fiber-reinforced composition (C) comprises, based on the total weight of the fiber-reinforced composition (C): a) 55.0-95.0 wt. %, preferably 55.0-90.0 wt. %, more preferably 60.0-85.0 wt. %, even more preferably 66.0-82.0 wt. %, for example 72.0-79.0 wt. % of a heterophasic polypropylene composition (HECO); b) 5.0 to 45.0% by weight, preferably 10.0 to 40.0% by weight, more preferably 12.0 to 35.0% by weight, even more preferably 14.0 to 29% by weight, for example 18.0 to 23.0% by weight of fibers (F); Includes.

[0029] According to a preferred embodiment of the invention, the fiber-reinforced composition (C) further comprises an adhesion promoter (AP).

[0030] Therefore, the fiber reinforced composition (C) is, based on the total weight of the fiber reinforced composition (C), a) 55.0 to 94.9 wt. %, preferably 55.0 to 90.0 wt. %, more preferably 60.0 to 85.0 wt. %, even more preferably 66.0 to 82.0 wt. %, for example 72.0 to 79.0 wt. % of a heterophasic polypropylene composition (HECO); b) 5.0 to 45.0% by weight, preferably 10.0 to 40.0% by weight, more preferably 12.0 to 35.0% by weight, even more preferably 14.0 to 29% by weight, for example 18.0 to 23.0% by weight of fibers (F); c) 0.1 to 5.0% by weight, preferably 0.3 to 4.8% by weight, more preferably 0.5 to 4.0% by weight, even more preferably 0.8 to 3.0% by weight, for example 1.0 to 2.0% by weight of an adhesion promoter (AP); It is preferred that the compound contains

[0031] The fiber-reinforced composition (C) according to the present invention may contain an additive (AD).

[0032] Therefore, the fiber-reinforced composition (C) according to the present invention has, based on the total weight of the fiber-reinforced composition (C), a) 55.0 to 94.9 wt. %, preferably 55.0 to 90.0 wt. %, more preferably 60.0 to 85.0 wt. %, even more preferably 66.0 to 82.0 wt. %, for example 72.0 to 79.0 wt. % of a heterophasic polypropylene composition (HECO); b) 5.0 to 45.0% by weight, preferably 10.0 to 40.0% by weight, more preferably 12.0 to 35.0% by weight, even more preferably 14.0 to 29% by weight, for example 18.0 to 23.0% by weight of fibers (F); c) 0.1 to 5.0% by weight, preferably 0.3 to 4.8% by weight, more preferably 0.5 to 4.0% by weight, even more preferably 0.8 to 3.0% by weight, for example 1.0 to 2.0% by weight of an adhesion promoter (AP); d) 0.01 to 2.5% by weight of an additive (AD); Preferably, the additive (AD) comprises, and more preferably consists of, the additive (AD) being described in more detail below.

[0033] Therefore, the fiber-reinforced composition (C) according to the present invention has, based on the total weight of the fiber-reinforced composition (C), a) 55.0 to 94.9 wt. % (e.g. 55.0 to 94.8 wt. %), preferably 55.0 to 90.0 wt. %, more preferably 60.0 to 85.0 wt. %, even more preferably 66.0 to 82.0 wt. %, for example 72.0 to 79.0 wt. % of a heterophasic polypropylene composition (HECO); b) 5.0 to 45.0% by weight, preferably 10.0 to 40.0% by weight, more preferably 12.0 to 35.0% by weight, even more preferably 14.0 to 29% by weight, for example 18.0 to 23.0% by weight of fibers (F); c) 0.1 to 5.0% by weight, preferably 0.3 to 4.8% by weight, more preferably 0.5 to 4.0% by weight, even more preferably 0.8 to 3.0% by weight, for example 1.0 to 2.0% by weight of an adhesion promoter (AP); d) 0.01 to 2.5% by weight of an additive (AD); The components a) to d) are preferably selected so that the total amount thereof is 100% by weight.

[0034] Furthermore, the fiber reinforced composition (C) according to the present invention may further comprise low density polyethylene (LDPE).

[0035] Thus, according to another embodiment of the present invention, the fiber-reinforced composition (C) comprises, based on the total weight of the fiber-reinforced composition (C): a) 55.0 to 94.9 wt. %, preferably 55.0 to 90.0 wt. %, more preferably 60.0 to 85.0 wt. %, even more preferably 66.0 to 82.0 wt. %, for example 72.0 to 79.0 wt. % of a heterophasic polypropylene composition (HECO); b) 5.0 to 25.0% by weight, preferably 10.0 to 22.0% by weight, more preferably 12.0 to 35.0% by weight, even more preferably 14.0 to 29% by weight, for example 18.0 to 23.0% by weight of fibers (F); c) 0.1 to 5.0% by weight, preferably 0.3 to 4.8% by weight, more preferably 0.5 to 4.0% by weight, even more preferably 0.8 to 3.0% by weight, for example 1.0 to 2.0% by weight of an adhesion promoter (AP); d) 0.0 to 20.0% by weight, preferably 5.0 to 18.0% by weight, more preferably 12.0 to 17.0% by weight, and even more preferably 13.0 to 16.0% by weight of low density polyethylene (LDPE); e) 0.01 to 2.5% by weight of additive (AD); and more preferably consists of these.

[0036] According to another embodiment of the present invention, the fiber reinforced composition (C) comprises, based on the total weight of the fiber reinforced composition (C), a) 55.0 to 94.9 wt. % (e.g. 55.0 to 94.8 wt. %), preferably 55.0 to 90.0 wt. %, more preferably 60.0 to 85.0 wt. %, even more preferably 66.0 to 82.0 wt. %, for example 72.0 to 79.0 wt. % of a heterophasic polypropylene composition (HECO); b) 5.0 to 25.0% by weight, preferably 10.0 to 22.0% by weight, more preferably 12.0 to 35.0% by weight, even more preferably 14.0 to 29% by weight, for example 18.0 to 23.0% by weight of fibers (F); c) 0.1 to 5.0% by weight, preferably 0.3 to 4.8% by weight, more preferably 0.5 to 4.0% by weight, even more preferably 0.8 to 3.0% by weight, for example 1.0 to 2.0% by weight of an adhesion promoter (AP); d) 0.0 to 20.0% by weight, preferably 5.0 to 18.0% by weight, more preferably 12.0 to 17.0% by weight, and even more preferably 13.0 to 16.0% by weight of low density polyethylene (LDPE); e) 0.01 to 2.5% by weight of additive (AD); and preferably consists of these, with components a) to d) being selected so that the total amounts to 100% by weight.

[0037] Preferably, the fiber reinforced composition (C) of the present invention does not contain (a) further polymer(s) different from the heterophasic polypropylene composition (HECO), the adhesion promoter (AP) and the optional low density polyethylene (LDPE) in an amount of more than 5.0% by weight, preferably more than 3.0% by weight, more preferably more than 2.5% by weight, based on the total weight of the fiber reinforced composition (C). One additional polymer that may be present in such a small amount is polyethylene, which is a reaction by-product obtained by preparing the heterophasic polypropylene composition (HECO). It is therefore specifically understood that the fiber reinforced composition (C) contains as polymeric compounds only the heterophasic polypropylene composition (HECO), the adhesion promoter (A), the optional low density polyethylene (LDPE) and, optionally, the polyethylene in the amounts mentioned in this paragraph.

[0038] The fiber reinforced composition (C) has a melt flow rate MFR2 (230°C, 2.16 kg) determined according to ISO 1133 in the range of 1.0 to 60.0 g / 10 min, more preferably in the range of 1.2 to 40.0 g / 10 min, even more preferably in the range of 2.0 to 35.0 g / 10 min, for example in the range of 2.5 to 29.0 g / 10 min.

[0039] According to one embodiment, the fiber reinforced composition (C) has a melt flow rate MFR2 (230 ° C, 2.16 kg) determined according to ISO 1133 in the range of 10.0 to 60.0 g / 10 min, more preferably in the range of 10.0 to 40.0 g / 10 min, even more preferably in the range of 10.0 to 35.0 g / 10 min, for example in the range of 10.0 to 29.0 g / 10 min (e.g. 20.0 to 29.0 g / 10 min). Melt flow rates in the range of 10.0 to 60.0 g / 10 min (and preferred subranges) are particularly preferred in combination with the "first embodiment of the invention" defined herein.

[0040] With regard to the mechanical properties, it is preferred that the fiber reinforced composition (C) has a tensile modulus, determined according to ISO 527-1A, of at least 2000 MPa, more preferably at least 2200 MPa, even more preferably at least 2300 MPa, such as at least 2400 MPa, and / or a tensile strength, determined according to ISO 527-2, of at least 40 MPa, more preferably at least 42 MPa, even more preferably at least 45 MPa, such as at least 50 MPa.

[0041] In addition or in place of the previous paragraph, it is preferred that the fiber reinforced composition has an elongation at break determined according to ISO 527-2 at 23° C. of at least 3.0%, more preferably at least 3.2%, even more preferably at least 3.4%.

[0042] The fiber reinforced composition (C) is preferably obtained by melt blending (melt mixing) the heterophasic polypropylene composition (HECO), the fibers (F), optionally an adhesion promoter (AP), optionally an additive (AD), and optionally a low density polyethylene (LDPE).

[0043] In the following, the heterophasic polypropylene composition (HECO), the fiber (F), the adhesion promoter (AP) and the low density polyethylene (LDPE) are described in more detail.

[0044] Heterophasic Polypropylene Composition (HECO) The fiber reinforced composition (C) of the present invention comprises a heterophasic polypropylene composition (HECO).

[0045] The heterophasic polypropylene composition (HECO) according to the invention comprises a matrix, which is a homopolymer or copolymer of propylene (PP), and an elastomeric ethylene copolymer (E) dispersed in the matrix. The matrix thus contains (finely) dispersed inclusions that are not part of the matrix, which inclusions contain the elastomeric copolymer (E). The term "inclusions" indicates that the matrix and the inclusions form different phases within the heterophasic polypropylene composition (HECO). The presence of second phases or so-called inclusions can be seen, for example, by high-resolution microscopy, such as electron microscopy or atomic force microscopy, or by dynamic mechanical thermal analysis (DMTA). In particular, in DMTA, the presence of a multiphase structure can be identified by the presence of at least two distinguishable glass transition temperatures.

[0046] Thus, the heterophasic polypropylene composition (HECO) according to the present invention preferably comprises: (a) a (semi)crystalline propylene homopolymer or copolymer (PP) as a matrix; (b) an elastomeric ethylene copolymer (E); Includes.

[0047] In particular, the heterophasic polypropylene composition (HECO) comprises, based on the total weight of the heterophasic polypropylene composition (HECO): (a) 60.0 to 95.0% by weight, more preferably 61.0 to 92.0% by weight, of a matrix which is a homopolymer or copolymer of propylene (PP); (b) 5.0 to 40.0% by weight, more preferably 8.0 to 39.0% by weight, of an elastomeric ethylene copolymer (E); It is preferred that the composition comprises, and more preferably consists of,

[0048] The heterophasic polypropylene composition (HECO) according to the present invention preferably has at least two distinct glass transition temperatures Tg(1) and Tg(2). In particular, the first glass transition temperature Tg(1) is preferably less than -15°C, more preferably less than -25°C. In addition, the second glass transition temperature Tg(2) is preferably at least -5°C, more preferably at least 0°C.

[0049] Preferably, the heterophasic polypropylene composition (HECO) has a melt flow rate MFR2 (230°C, 2.16 kg) determined according to ISO 1133 in the range of 5.0 to 100 g / 10 min, more preferably in the range of 6.0 to 95.0 g / 10 min, even more preferably in the range of 7.0 to 87.0 g / 10 min, for example in the range of 8.0 to 80.0 g / 10 min.

[0050] Furthermore, it is preferred that the heterophasic polypropylene composition (HECO) has an intrinsic viscosity (IV) measured according to ISO 1628 / 1 (135°C in decalin) of the soluble fraction (SF) determined according to CRYSTEX QC in the range of 1.8-3.0 dl / g, more preferably in the range of 2.5-3.0 dl / g.

[0051] Preferably, the heterophasic polypropylene composition (HECO) is thermomechanically stable. It is therefore understood that the heterophasic polypropylene composition (HECO) has a melting temperature Tm determined according to differential scanning calorimetry (DSC) in the range of 130-165°C, preferably in the range of 130-160°C, more preferably in the range of 130-159°C, even more preferably in the range of 132-159°C, even more preferably in the range of 135-158°C, for example in the range of 139-157°C.

[0052] The propylene homopolymer or copolymer (PP) has an amount of 1,2 erythro site defects of at least 0.4 mol%, preferably in the range of 0.4-1.2 mol%. Without being bound by theory, the large amount of misinsertion of propylene in the polymer chain indicates that the propylene homopolymer or copolymer (PP) is produced in the presence of a single-site catalyst, preferably a metallocene catalyst. For example, it is known in the art that propylene homopolymers or copolymers produced in the presence of a Ziegler-Natta catalyst can have an amount of 1,2 erythro site defects well below 0.4 mol%, and in many cases are essentially free of 1,2 erythro site defects.

[0053] The heterophasic polypropylene composition (HECO) also contains comonomers other than propylene. Preferably, the heterophasic polypropylene composition (HECO) also contains ethylene and / or C4-C 12 Contains α-olefins.

[0054] Thus, the term "copolymer of propylene" according to the present invention means (a) propylene, and (b) Ethylene and / or C4-C 12 Alpha-Olefin is understood as polypropylene comprising, and preferably consisting of, units derivable from

[0055] Furthermore, the term "ethylene copolymer" according to the present invention means (a) Ethylene and (b) C3~C 12 Alpha-Olefin is understood as polyethylene comprising, and preferably consisting of, units derivable from

[0056] Thus, the matrix of the propylene homopolymer or copolymer (PP), i.e. the heterophasic polypropylene composition (HECO), is composed of monomers copolymerizable with propylene, such as ethylene and / or C4-C612 The elastomeric ethylene copolymer (E) may contain comonomers such as α-olefins, in particular ethylene and / or C4-C8 α-olefins, such as 1-butene and / or 1-hexene. The elastomeric ethylene copolymer (E) may contain comonomers such as monomers copolymerizable with ethylene, such as C3-C 12 It may contain comonomers such as α-olefins, in particular propylene, 1-butene, 1-hexene and / or 1-octene. More specifically, the heterophasic polypropylene composition (HECO) of the present invention comprises units derivable from 1-butene, 1-hexene and / or 1-octene in addition to propylene and ethylene.

[0057] Thus, the propylene homopolymer or copolymer (PP) according to the present invention can be a propylene homopolymer or a propylene copolymer.

[0058] In particular, it is preferred that the propylene homopolymer or copolymer (PP) has a comonomer content, preferably an ethylene content, of 8.5 mol % or less, more preferably in the range of 0.0 to 8.3 mol %, even more preferably in the range of 0.0 to 8.0 mol %, for example in the range of 0.0 to 6.0 mol %.

[0059] The elastomeric ethylene copolymer (E) according to the present invention is prepared by copolymerizing monomers copolymerizable with ethylene, such as C3-C 12 It comprises a comonomer such as an α-olefin, in particular propylene, 1-butene, 1-hexene and / or 1-octene. Preferably, the elastomeric ethylene copolymer (E) has an ethylene content in the range of 15.0 to 85.0 wt.%, more preferably in the range of 18.0 to 82.0 wt.%, even more preferably in the range of 19.0 to 79.0 wt.%, for example in the range of 20.0 to 76.0 wt.%, based on the total weight of the elastomeric ethylene copolymer (E).

[0060] According to a first embodiment of the invention, the homopolymer or copolymer of propylene (PP) is preferably a propylene homopolymer (hPP).

[0061] The expression "propylene homopolymer" as used herein relates to a polypropylene consisting essentially, i.e. at least 99.0% by weight, more preferably at least 99.5% by weight, even more preferably at least 99.8% by weight, such as at least 99.9% by weight, of propylene units. In another embodiment, only propylene units are detectable, i.e. only propylene is polymerized.

[0062] Thus, according to a first embodiment of the present invention, the heterophasic polypropylene composition (HECO) comprises: a) a matrix which is a propylene homopolymer (hPP); b) an elastomeric ethylene copolymer (E); Includes.

[0063] The elastomeric ethylene copolymer (E) according to the first embodiment of the present invention is a copolymerizable monomer with ethylene, for example a C3-C 12 and comonomers such as α-olefins, in particular propylene, 1-butene, 1-hexene and / or 1-octene. According to the first embodiment of the invention, it is particularly preferred that the elastomeric ethylene copolymer (E) is a copolymer of ethylene and propylene. In other words, the elastomeric ethylene copolymer (E) according to the first embodiment of the invention only comprises units derivable from ethylene and propylene.

[0064] Therefore, the heterophasic polypropylene composition (HECO) according to the first embodiment of the present invention preferably comprises only units derivable from ethylene and propylene.

[0065] Preferably, the heterophasic polypropylene composition (HECO) according to the first embodiment of the present invention has a comonomer content, preferably an ethylene content, in the range of 2.2 to 8.7 mol %, more preferably in the range of 2.7 to 5.8 mol %, even more preferably in the range of 2.9 to 4.4 mol %.

[0066] Furthermore, the heterophasic polypropylene composition (HECO) according to the first embodiment of the present invention preferably has a xylene cold solubles (XCS) content, determined at 25°C according to ISO 16152, in the range of 5.0 to 35.0 wt.%, more preferably in the range of 7.0 to 20.0 wt.%, even more preferably in the range of 9.0 to 15.0 wt.%, for example in the range of 10.0 to 12.0 wt.%, based on the total weight of the heterophasic polypropylene composition (HECO) according to the first embodiment of the present invention.

[0067] Additionally or alternatively, said xylene cold soluble (XCS) fraction of the heterophasic polypropylene composition (HECO) according to the first embodiment of the present invention preferably has a comonomer content, preferably an ethylene content, in the range of 20.9-44.7 mol %, more preferably in the range of 25.0-40.0 mol %, even more preferably in the range of 28.0-38.0 mol %, such as in the range of 30.0-34.0 mol %.

[0068] Preferably, the heterophasic polypropylene composition (HECO) according to the first embodiment of the present invention has an intrinsic viscosity (IV) measured according to ISO 1628 / 1 (135° C. in Decalin) of the xylene cold soluble (XCS) fraction in the range of 1.8 to 3.0 dl / g, more preferably in the range of 2.2 to 2.8 dl / g, even more preferably in the range of 2.3 to 2.7 dl / g.

[0069] In addition or instead of the previous paragraphs, it is understood that the heterophasic polypropylene composition (HECO) according to the first embodiment of the present invention preferably has a soluble fraction (SF) determined according to CRYSTEX QC in the range of 5.0-35.0 wt.%, more preferably in the range of 7.0-20.0 wt.%, even more preferably in the range of 9.0-15.0 wt.%, for example in the range of 10.0-12.0 wt.%, based on the total weight of the heterophasic polypropylene composition (HECO) according to the first embodiment of the present invention.

[0070] The comonomer content, preferably the ethylene content, of the soluble fraction (SF) determined according to CRYSTEX QC of the heterophasic polypropylene composition (HECO) according to the first embodiment of the present invention is preferably in the range of 20.9-44.7 mol%, more preferably in the range of 25.0-40.0 mol%, even more preferably in the range of 28.0-38.0 mol%, for example in the range of 30.0-34.0 mol%.

[0071] Preferably, the heterophasic polypropylene composition (HECO) according to the first embodiment of the present invention has an intrinsic viscosity (IV) measured according to ISO 1628 / 1 (135° C. in Decalin) of the soluble fraction (SF) determined according to CRYSTEX QC in the range of 1.8 to 3.0 dl / g, more preferably in the range of 2.2 to 2.8 dl / g, even more preferably in the range of 2.3 to 2.7 dl / g.

[0072] The heterophasic polypropylene composition (HECO) according to the first embodiment of the present invention preferably has a medium melt flow rate. Therefore, the heterophasic polypropylene composition (HECO) according to the first embodiment of the present invention preferably has a melt flow rate MFR2 (230°C, 2.16 kg) determined according to ISO 1133 in the range of 20.0 to 100.0 g / 10 min, more preferably in the range of 45.0 to 95.0 g / 10 min, even more preferably in the range of 56.0 to 90.0 g / 10 min, for example in the range of 70.0 to 80.0 g / 10 min.

[0073] Furthermore, the heterophasic polypropylene composition (HECO) according to the first embodiment of the present invention has a melting temperature Tm determined according to differential scanning calorimetry (DSC) in the range of 130-165°C, preferably in the range of 130-160°C, more preferably in the range of 135-160°C, even more preferably in the range of 145-159°C, for example in the range of 152-157°C.

[0074] Concerning the mechanical properties, the heterophasic polypropylene composition (HECO) according to the first embodiment of the present invention preferably has a flexural modulus determined according to ISO 178 in the range of 500-2000 MPa, more preferably in the range of 800-1900 MPa, even more preferably in the range of 1000-1500 MPa, for example in the range of 1100-1300 MPa.

[0075] In addition or alternatively to the previous paragraph, the heterophasic polypropylene composition (HECO) according to the first embodiment of the present invention has a thermal expansion coefficient of at least 1.5 kJ / m 2 , more preferably at least 2.5 kJ / m 2 , and even more preferably at least 3.0 kJ / m 2 , e.g. at least 3.5 kJ / m 2 and / or a notched Charpy impact strength determined at 23°C in accordance with ISO 179 / 1eA of at least 0.5 kJ / m 2 , more preferably at least 0.8 kJ / m 2 , and even more preferably at least 1.3 kJ / m 2 , e.g. at least 1.7 kJ / m 2 It is preferred that the ferroelectric material has a Charpy notched impact strength determined at -20°C in accordance with ISO 179 / 1eA of 100%.

[0076] Furthermore, the fiber reinforced composition (C) according to the first embodiment of the present invention preferably has a tensile modulus determined according to ISO 527-1A in the range of 3000 to 6000 MPa (for example, in the range of 4200 to 6000 MPa), more preferably in the range of 3500 to 5800 MPa, even more preferably in the range of 4200 to 5300 MPa, for example in the range of 4700 to 5000 MPa.

[0077] Additionally or alternatively, the fiber reinforced composition (C) according to the first embodiment of the present invention preferably has an elongation at break determined according to ISO 527-2 of more than 3.0%, more preferably more than 3.2%, even more preferably more than 3.3%, such as more than 3.4%.

[0078] The heterophasic polypropylene composition (HECO) according to the first embodiment of the present invention can be further defined by its individual components: the matrix, which is a propylene homopolymer (hPP), and the elastomeric ethylene copolymer (E), which is a copolymer of ethylene and propylene.

[0079] The matrix, which is a propylene homopolymer (hPP), preferably has a melt flow rate MFR2 (230°C, 2.16 kg) determined according to ISO 1133 in the range of 30.0 to 200 g / 10 min, more preferably in the range of 40.0 to 110 g / 10 min, even more preferably in the range of 60.0 to 95.0 g / 10 min, for example in the range of 75.0 to 85.0 g / 10 min.

[0080] Preferably, the propylene homopolymer (hPP) has a melting temperature Tm, determined according to differential scanning calorimetry (DSC), in the range of 140 to 160°C, more preferably in the range of 142 to 159°C, even more preferably in the range of 145 to 158°C, for example in the range of 147 to 157°C.

[0081] The propylene homopolymer (hPP) has an amount of 1,2 erythro regio-defects of at least 0.4 mol %, which indicates that the propylene homopolymer (PP) is produced in the presence of a single-site catalyst, preferably a metallocene catalyst, as outlined above.

[0082] As described in more detail below, the heterophasic polypropylene composition (HECO) according to the first embodiment of the present invention is preferably obtained in a sequential (continuous) process in the presence of a metallocene catalyst. It is therefore particularly preferred that the propylene homopolymer (hPP) and the elastomeric ethylene copolymer (E) are prepared in a sequential process in the presence of a metallocene catalyst.

[0083] Therefore, the elastomeric ethylene copolymer (E) according to the first embodiment of the present invention, which is a copolymer of ethylene and propylene, also preferably has 1,2 erythro position defects in an amount of at least 0.4 mol % (preferably in the range of 0.4 to 1.2 mol %).

[0084] The heterophasic polypropylene composition (HECO) according to the first embodiment of the present invention preferably comprises i) a matrix which is 60.0 to 99.0% by weight, more preferably 75.0 to 98.0% by weight, even more preferably 80.0 to 95.0% by weight, for example 85.0 to 90.0% by weight, of propylene homopolymer (hPP); ii) 1.0 to 40.0 wt. %, more preferably 2.0 to 25.0 wt. %, even more preferably 5.0 to 20.0 wt. %, for example 10.0 to 15.0 wt. % of an elastomeric ethylene copolymer (E) which is a copolymer of ethylene and propylene; Includes.

[0085] The heterophasic polypropylene composition (HECO) according to the first embodiment of the present invention can be prepared by blending, preferably melt blending, propylene homopolymer (hPP) and elastomeric ethylene copolymer (E) together or by producing propylene homopolymer (hPP) and elastomeric ethylene copolymer (E) in a sequential process, the latter being preferred.

[0086] The process for the preparation of a heterophasic polypropylene composition (HECO) according to the first embodiment of the present invention is preferably a sequential polymerization process comprising at least two reactors connected in series, the process comprising: (A) polymerizing propylene in a first reactor (R-1), which is a slurry reactor (SR), preferably a loop reactor (LR), to obtain a first fraction of propylene homopolymer (hPP) as defined in the present invention; (B) transferring the first fraction of said propylene homopolymer (hPP) from the first reactor (R-1) to a second reactor (R-2), which is a gas phase reactor (GPR-1); (C) supplying propylene to the second reactor (R-2); (D) polymerizing propylene in the presence of the first fraction of propylene homopolymer (hPP) in the second reactor (R-2) to obtain a second fraction of propylene homopolymer (hPP), wherein the first and second fractions form the propylene homopolymer (hPP) of the present invention; (E) transferring the propylene homopolymer (hPP) in the second reactor (R-2) to a third reactor (R-3), which is a gas phase reactor (GPR-2); (F) In the third reactor (R-3), propylene, ethylene and C4 to C 12 providing a comonomer selected from an α-olefin, preferably ethylene; (G) In the third reactor (R-3), propylene, ethylene and C4 to C6 propylene are reacted in the presence of the propylene homopolymer (hPP). 12 polymerizing a comonomer selected from an α-olefin, preferably ethylene, to obtain an elastomeric ethylene copolymer (E) as defined in the present invention, said propylene homopolymer (hPP) and said elastomeric ethylene copolymer (E) forming a heterophasic polypropylene composition (HECO) as defined in the present invention; and In the first reactor (R-1), the second reactor (R-2) and the third reactor (R-3), polymerization takes place in the presence of a solid catalyst system (SCS).

[0087] A solid catalyst system (SCS) is defined in more detail below.

[0088] The term "sequential polymerization process" means that the heterophasic polypropylene composition (HECO) according to the first embodiment of the invention is produced in at least two reactors connected in series. More precisely, the term "sequential polymerization process" indicates in the present application that the polymer of the first reactor (R-1) is directly conveyed to the second reactor (R-2) together with the unreacted monomers. The crucial aspect of the process is therefore the preparation of the heterophasic polypropylene composition (HECO) in at least two different reactors, the reacting material of the first reactor (R-1) being directly conveyed to the second reactor (R-2). The process therefore comprises at least a first reactor (R-1) and a second reactor (R-2). In one particular embodiment, the process consists of three polymerization reactors (R-1), (R-2) and (R-3). The term "polymerization reactor" is intended to indicate that the main polymerization takes place therein. Thus, if the process consists of three polymerization reactors, this definition does not exclude the option that the overall process comprises a prepolymerization step, for example in a prepolymerization reactor. The term "consists of" is merely a closing formulation taking into account the main polymerization reactors.

[0089] The first reactor (R-1) is a slurry reactor (SR) and can be any continuous or simply stirred batch tank reactor or loop reactor operating with a slurry. According to the invention, the slurry reactor (SR) is preferably a loop reactor (LR).

[0090] The second reactor (R-2), the third reactor (R-3) and any subsequent reactors are gas phase reactors (GPR). Such gas phase reactors (GPR) can be any mechanically mixed reactor or fluidized bed reactor. Preferably, the gas phase reactors (GPR) comprise mechanically stirred fluidized bed reactors having a gas velocity of at least 0.2 m / sec. It is therefore understood that the gas phase reactors (GPR) are preferably fluidized bed type reactors equipped with mechanical stirrers.

[0091] The conditions in each reactor (temperature, pressure, reaction time, monomer feed) depend on the desired product and are within the knowledge of the skilled person. As already indicated above, the first reactor (R-1) is a slurry reactor (SR), e.g., a loop reactor (LR), whereas the second reactor (R-2) and the third reactor (R-3) are gas phase reactors (GPR-1) and (GPR-2). Subsequent reactors, if present, are also gas phase reactors (GPR).

[0092] A preferred multi-stage process is a "loop-gas phase" process such as that developed by Borealis A / S, Denmark (known as BORSTAR® technology) and described in patent documents such as, for example, EP 0 887 379 or WO 92 / 12182.

[0093] Multimodal polymers can be produced according to several processes described, for example, in WO 92 / 12182, EP 0 887 379 and WO 98 / 58976, the contents of which are incorporated herein by reference.

[0094] Preferably, in the process for producing a heterophasic polypropylene composition (HECO) as defined above, the conditions for the first reactor (R-1) of step (A), i.e. the slurry reactor (SR), e.g. the loop reactor (LR), may be as follows: the temperature is in the range of 40°C to 110°C, preferably between 60°C and 100°C, more preferably in the range of 65°C to 90°C, the pressure is in the range of 20 bar to 80 bar, preferably between 40 bar and 70 bar; Hydrogen can be added to control the molar mass in a manner known per se.

[0095] Subsequently, the reaction mixture from step (A) is transferred to the second reactor (R-2), i.e., the gas phase reactor (GPR-1), i.e., step (D), wherein the conditions in step (D) are preferably as follows: The temperature is in the range of 50°C to 130°C, preferably between 60°C and 100°C, the pressure is in the range of 5 bar to 50 bar, preferably between 15 bar and 40 bar, Hydrogen can be added to control the molar mass in a manner known per se.

[0096] The residence time may be different in both reactor zones.

[0097] In one embodiment of the process for the production of the heterophasic polypropylene composition (HECO), the residence time in the slurry reactor (SR), e.g., loop (LR), ranges from 0.2 to 4.0 hours, e.g., 0.3 to 1.5 hours, and the residence time in the gas phase reactor (GPR) is generally from 0.2 to 6.0 hours, e.g., 0.5 to 4.0 hours.

[0098] If desired, the polymerization may be carried out in a known manner under supercritical conditions in a first reactor (R-1), ie in a slurry reactor (SR), for example in a loop reactor (LR).

[0099] The conditions in the third reactor (R-3), i.e. the second gas phase reactor (GPR-2), and any other subsequent gas phase reactors (GPRs), if present, are similar to those in the second reactor (R-2).

[0100] The process may also include a prepolymerization prior to the polymerization in the first reactor (R-1). This prepolymerization can take place in the first reactor (R-1), however, it is preferred that the prepolymerization takes place in a separate reactor, the so-called prepolymerization reactor.

[0101] The heterophasic polypropylene composition (HECO) according to a first embodiment of the present invention is prepared in the presence of a solid catalyst system (SCS) comprising a transition metal compound.

[0102] It is particularly preferred that the solid catalyst system (SCS) is a metallocene catalyst comprising a metallocene complex, a cocatalyst system comprising a boron-containing cocatalyst and / or an aluminoxane cocatalyst, and a silica support. In particular, the metallocene catalyst is (i) A metallocene complex of general formula (I), [ka] In the above formula (I), each X is independently a σ-donor ligand; L is a divalent bridging group selected from -R'2C-, -R'2C-CR'2-, -R'2Si-, -R'2Si-SiR'2-, -R'2Ge-, and each R' is independently a hydrogen atom or a C1-C aryl group optionally containing one or more heteroatoms or fluorine atoms from groups 14 to 16 of the periodic table. 20 - a hydrocarbyl group, or optionally two R' groups can be taken together to form a ring; Each R 1 can be independently the same or different and are hydrogen, a linear or branched C1-C6 alkyl group, C 7~20 -aryl alkyl, C 7~20 -alkylaryl group or C 6~20 -aryl group or OY group, Y is C 1~10 -hydrocarbyl group, optionally with two adjacent R 1 The groups can be part of a ring that includes the phenyl carbon to which they are attached; Each R 2 can be independently the same or different, and CH-R 8 is a group, R 8 is H or a linear or branched C 1~6 -Alkyl group, C 3~8 -Cycloalkyl group, C 6~10 -aryl group, R 3is a linear or branched C1-C6 alkyl group, C 7~20 -aryl alkyl, C 7~20 -Alkylaryl group or C6-C 20 -aryl group, R 4 is C(R 9 ) 3 groups, R 9 is a linear or branched C1-C6 alkyl group, R 5 is hydrogen or an aliphatic C1-C which may contain one or more heteroatoms from groups 14 to 16 of the periodic table; 20 - a hydrocarbyl group, R 6 is hydrogen or an aliphatic C1-C which may contain one or more heteroatoms from groups 14 to 16 of the periodic table; 20 - a hydrocarbyl group, or R 5 and R 6 together form n groups R 10 wherein n is 0 to 4, Each R 10 are the same or different, C1 to C 20 - a hydrocarbyl group or a C1-C group which may contain one or more heteroatoms belonging to groups 14 to 16 of the periodic table 20 -hydrocarbyl group, R 7 is H or a linear or branched C1-C6-alkyl group or 1-3 groups R 11 is an aryl or heteroaryl group having 6 to 20 carbon atoms, optionally substituted by Each R 11 can be independently the same or different and are hydrogen, a linear or branched C1-C6 alkyl group, C 7~20 -aryl alkyl, C 7~20 -alkylaryl group or C 6~20 -aryl group or OY group, Y is C 1~10 - is a hydrocarbyl group A metallocene complex; (ii) a cocatalyst system comprising a boron-containing cocatalyst and / or an aluminoxane cocatalyst; (iii) a silica support; It is preferred that the compound contains

[0103] The term "sigma-donor ligand" is well understood to those skilled in the art, i.e., a group that is bonded to a metal via a sigma bond. Thus, the anionic ligand "X" can independently be a halogen or may be selected from the group consisting of R', OR', SiR'3, OSiR'3, OSO2CF3, OCOR', SR', NR'2, or PR'2 groups, where R' is independently hydrogen, linear or branched, cyclic or acyclic, C1-C 20 Alkyl, C2-C 20 Alkenyl, C2-C 20 Alkynyl, C3-C 12 Cycloalkyl, C6-C 20 Aryl, C7-C 20 Aryl alkyl, C7-C 20 Alkylaryl, C8-C 20 Arylalkenyl, where the R' group can optionally contain one or more heteroatoms belonging to groups 14 to 16. In a preferred embodiment, the anionic ligands "X" are the same and are either halogen, e.g., Cl, or methyl or benzyl.

[0104] Preferred monovalent anionic ligands are the halogens, especially chlorine (Cl).

[0105] Preferred metallocene complexes include rac-Dimethylsilanediylbis[2-methyl-4-(3',5'-dimethylphenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride, rac-anti-dimethylsilanediyl[2-methyl-4-(4'-tert-butylphenyl)-inden-1-yl][2-methyl-4-(4'-tert-butylphenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride, rac-anti-dimethylsilanediyl[2-methyl-4-(4'-tert-butylphenyl)-inden-1-yl][2-methyl-4-phenyl-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride, rac-anti-dimethylsilanediyl[2-methyl-4-(3',5'-tert-butylphenyl)-1,5,6,7-tetrahydro-s-indacen-1-yl][2-methyl-4-(3',5'-dimethyl-phenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride, rac-anti-dimethylsilanediyl[2-methyl-4,8-bis-(4'-tert-butylphenyl)-1,5,6,7-tetrahydro-s-indacen-1-yl][2-methyl-4-(3',5'-dimethyl-phenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride, rac-anti-dimethylsilanediyl[2-methyl-4,8-bis-(3',5'-dimethylphenyl)-1,5,6,7-tetrahydro-s-indacen-1-yl][2-methyl-4-(3',5'-dimethylphenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride, rac-anti-dimethylsilanediyl[2-methyl-4,8-bis-(3',5'-dimethylphenyl)-1,5,6,7-tetrahydro-s-indacen-1-yl][2-methyl-4-(3',5'-5-tert-butyl-phenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride Examples include:

[0106] Particularly preferred is rac-anti-dimethylsilanediyl[2-methyl-4,8-bis-(3',5'-dimethylphenyl)-1,5,6,7-tetrahydro-s-indacen-1-yl][2-methyl-4-(3',5'-dimethylphenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride (II). [ka]

[0107] The ligands required to form the complexes and thus the catalysts of the present invention can be synthesized by any process, and an organic chemist skilled in the art will be able to devise various synthesis protocols to produce the required ligand materials. For example, WO 2007 / 116034 discloses the necessary chemical reactions. Synthesis protocols can also be found generally in WO 2002 / 02576, WO 2011 / 135004, WO 2012 / 084961, WO 2012 / 001052, WO 2011 / 076780, WO 2015 / 158790 and WO 2018 / 122134. In particular, reference is made to WO 2019 / 179959, in which the most preferred catalysts of the present invention are described.

[0108] In accordance with the present invention, a cocatalyst system comprising a boron-containing cocatalyst and / or an aluminoxane cocatalyst is used in combination with the metallocene catalyst complex defined above.

[0109] The aluminoxane cocatalyst can be of formula (III). [ka] In formula (III), n is usually 6 to 20, and R has the following meaning.

[0110] Aluminoxanes are formed by partial hydrolysis of organoaluminum compounds, such as compounds of formulae AlR3, AlR2Y and Al2R3Y3, where R is, for example, C1-C 10 -alkyl, preferably C1-C5-alkyl, or C3-C 10 -Cycloalkyl, C7-C 12 -arylalkyl or C7-C 12-alkylaryl, and / or phenyl or naphthyl, where Y is hydrogen, halogen, preferably chlorine or bromine, or C1-C 10 -alkoxy, preferably methoxy or ethoxy. The oxygen-containing aluminoxanes obtained are generally not pure compounds but are mixtures of oligomers of formula (III).

[0111] A preferred aluminoxane is methylaluminoxane (MAO). The aluminoxanes used as cocatalysts according to the present invention are not pure compounds due to the manner of their preparation, so the molar concentrations of the aluminoxane solutions hereinafter are based on their aluminum content.

[0112] According to the present invention, a boron-containing cocatalyst can also be used in place of the aluminoxane cocatalyst, or the aluminoxane cocatalyst can be used in combination with a boron-containing cocatalyst.

[0113] Those skilled in the art will appreciate that when a boron-based cocatalyst is used, it is common to pre-alkylate the complex by reaction with an aluminum alkyl compound such as TIBA. This procedure is well known and any suitable aluminum alkyl can be used, such as Al(C1-C6 alkyl)3. Preferred aluminum alkyl compounds are triethylaluminum, triisobutylaluminum, triisohexylaluminum, tri-n-octylaluminum and triisooctylaluminum.

[0114] Alternatively, when a borate (boron ate complex) cocatalyst is used, the metallocene catalyst complex can be an alkylated version thereof, ie, for example, a dimethyl or dibenzyl metallocene catalyst complex can be used.

[0115] Boron-based cocatalysts of interest include those of formula (IV): BY3(IV) In formula (IV), Y is the same or different and is a hydrogen atom, an alkyl group having 1 to about 20 carbon atoms, an aryl group having 6 to about 15 carbon atoms, an alkylaryl having 1 to 10 carbon atoms in the alkyl radical and 6 to 20 carbon atoms in the aryl radical, an arylalkyl, a haloalkyl or a haloaryl, or a fluorine, chlorine, bromine or iodine. Preferred examples of Y are methyl, propyl, isopropyl, isobutyl or trifluoromethyl, unsaturated groups such as aryl or haloaryl, for example phenyl, tolyl, benzyl group, p-fluorophenyl, 3,5-difluorophenyl, pentachlorophenyl, pentafluorophenyl, 3,4,5-trifluorophenyl and 3,5-di(trifluoromethyl)phenyl. Preferred choices are trifluoroborane, triphenylborane, tris(4-fluorophenyl)borane, tris(3,5-difluorophenyl)borane, tris(4-fluoromethylphenyl)borane, tris(2,4,6-trifluorophenyl)borane, tris(pentafluorophenyl)borane, tris(tolyl)borane, tris(3,5-dimethyl-phenyl)borane, tris(3,5-difluorophenyl)borane and / or tris(3,4,5-trifluorophenyl)borane.

[0116] Particularly preferred is tris(pentafluorophenyl)borane.

[0117] However, it is preferred to use borate, i.e. compounds containing borate 3+ ions. Such ionic cocatalysts preferably contain non-coordinating anions such as tetrakis(pentafluorophenyl)borate and tetraphenylborate. Suitable counterions are protonated amine or aniline derivatives, such as methylammonium, anilinium, dimethylammonium, diethylammonium, N-methylanilinium, diphenylammonium, N,N-dimethylanilinium, trimethylammonium, triethylammonium, tri-n-butylammonium, methyldiphenylammonium, pyridinium, p-bromo-N,N-dimethylanilinium or p-nitro-N,N-dimethylanilinium.

[0118] Preferred ionic compounds that can be used in accordance with the present invention include the following: triethylammonium tetra(phenyl)borate, tributylammonium tetra(phenyl)borate, trimethylammonium tetra(tolyl)borate, tributylammonium tetra(tolyl)borate, tributylammonium tetra(pentafluorophenyl)borate, tripropylammonium tetra(dimethylphenyl)borate, tributylammonium tetra(trifluoromethylphenyl)borate, tributylammonium tetra(4-fluorophenyl)borate, N,N-dimethylcyclohexylammonium tetrakis(pentafluorophenyl)borate, N,N-dimethylbenzylammonium tetrakis(pentafluorophenyl)borate, N,N-dimethylanilinium tetra(phenyl)borate, N,N-diethylanilinium tetra(phenyl)borate, N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate, N,N-di(propyl)ammonium tetrakis(pentafluorophenyl)borate, di(cyclohexyl)ammonium tetrakis(pentafluorophenyl)borate, triphenylphosphonium tetrakis(phenyl)borate, triethylphosphonium tetrakis(phenyl)borate, diphenylphosphonium tetrakis(phenyl)borate, tri(methylphenyl)phosphonium tetrakis(phenyl)borate, tri(dimethylphenyl)phosphonium tetrakis(phenyl)borate, triphenylcarbenium tetrakis(pentafluorophenyl)borate, or Ferrocenium tetrakis(pentafluorophenyl)borate).

[0119] The preferred triphenylcarbenium tetrakis(pentafluorophenyl)borate, N,N-dimethylcyclohexylammonium tetrakis(pentafluorophenyl)borate, or N,N-Dimethylbenzylammonium tetrakis(pentafluorophenyl)borate It is.

[0120] Surprisingly, it has been found that certain boron cocatalysts are particularly preferred. Thus, the preferred borates used in the present invention contain trityl ions. Thus, the use of N,N-dimethylammonium-tetrakispentafluorophenylborate and Ph3CB(PhF5)4 and analogs thereof is particularly preferred.

[0121] According to the present invention, preferred cocatalysts are aluminoxanes, more preferably methylaluminoxane, combinations of aluminoxanes with Al alkyls, boron or borate cocatalysts, and combinations of aluminoxanes with boron-based cocatalysts.

[0122] Suitable amounts of cocatalyst are well known to those skilled in the art. The molar ratio of boron to the metal ion of the metallocene may range from 0.5:1 to 10:1 mol / mol, preferably from 1:1 to 10:1, especially from 1:1 to 5:1 mol / mol. The molar ratio of Al in the aluminoxane to the metal ion of the metallocene may be in the range of 1:1 to 2000:1 mol / mol, preferably 10:1 to 1000:1, more preferably 50:1 to 500:1 mol / mol.

[0123] The catalyst can be used in supported or unsupported form, preferably in supported form.The particulate support material used is preferably an organic or inorganic material, such as silica, alumina or zirconia, or a mixed oxide, such as silica-alumina, in particular silica, alumina or silica-alumina.The use of silica supports is preferred.Those skilled in the art are aware of the procedures required for supporting metallocene catalysts.

[0124] Especially preferably, the support is a porous material, so that the complex may be loaded into the pores of the support using processes similar to those described, for example, in WO 94 / 14856 (Mobil), WO 95 / 12622 (Borealis) and WO 2006 / 097497.

[0125] The average particle size (average particle size) of the silica support can typically be 10-100 μm. However, it has been found that particular advantages are obtained when the support has a median particle size d50 of 15-80 μm, preferably 18-50 μm. The average pore size of the silica support can be in the range of 10-100 nm and the pore volume can be 1-3 mL / g.

[0126] Examples of suitable support materials are, for example, ES757 manufactured and sold by PQ Corporation, Sylopol 948 manufactured and sold by Grace, or SUNSPERA DM-L-303 silica manufactured by AGC Si-Tech Co. The support can be optionally calcined prior to use in the catalyst preparation to reach an optimal silanol group content.

[0127] The use of these carriers is well known in the art.

[0128] According to a second embodiment of the invention, the propylene homo- or copolymer (PP) which is the matrix of the heterophasic polypropylene composition (HECO) is a propylene copolymer (cPP).

[0129] The heterophasic polypropylene composition (HECO) according to the second embodiment of the present invention preferably has a fairly low melt flow rate. Preferably, the melt flow rate MFR2 (230°C, 2.16 kg) determined according to ISO 1133 of the heterophasic polypropylene composition (HECO) according to the second embodiment of the present invention is in the range of 5.0 to 20.0 g / 10 min, more preferably in the range of 6.0 to 15.0 g / 10 min.

[0130] The heterophasic polypropylene composition (HECO) according to the second embodiment of the present invention comprises, based on the total weight of the heterophasic polypropylene composition (HECO): i) 40.0 to 90.0 wt.%, more preferably 45.0 to 85.0 wt.%, even more preferably 56.0 to 74.0 wt.%, for example 58.0 to 65.0 wt.% of a propylene copolymer (cPP); ii) 10.0 to 60.0 wt. %, more preferably 15.0 to 55.0 wt. %, even more preferably 26.0 to 44.0 wt. %, for example 35.0 to 42.0 wt. % of an elastomeric ethylene copolymer (E); It is preferred that the compound contains

[0131] The propylene copolymer (cPP) preferably comprises comonomers copolymerizable with propylene, such as ethylene and / or C4-C8 α-olefins, in particular ethylene and / or C4-C6 α-olefins, such as 1-butene and / or 1-hexene. Preferably, the propylene copolymer (cPP) comprises, in particular consists of, monomers copolymerizable with propylene from the group consisting of ethylene, 1-butene and 1-hexene. More specifically, the propylene copolymer (cPP) comprises, besides propylene, units derivable from ethylene and / or 1-butene. Thus, in a particularly preferred embodiment, the propylene copolymer (cPP) comprises only units derivable from ethylene and propylene.

[0132] In particular, it is preferred that the propylene copolymer (cPP) is a random propylene copolymer, for example a random copolymer of propylene and ethylene.

[0133] The term "random copolymer" should preferably be understood according to IUPAC (Pure Appl. Chem., Vol. 68, No. 8, pp. 1591-1595, 1996). Preferably, the molar concentrations of the comonomer dyads, for example the ethylene dyads, obey the following relationship: [HH]<[H] 2 During the ceremony, [HH] is the mole fraction of adjacent comonomer units, e.g., adjacent ethylene units; [H] is the mole fraction of all comonomer units, e.g., all ethylene units, in the polymer.

[0134] Preferably, the propylene copolymer (cPP) has a comonomer content, such as an ethylene content, in the range of 2.2 to 8.5 mol%, more preferably in the range of 2.5 to 6.0 mol%, even more preferably in the range of 3.0 to 4.8 mol%, for example in the range of 3.5 to 4.0 mol%.

[0135] Further, it is preferred that the propylene copolymer (cPP) has a melt flow rate MFR2 (230°C, 2.16 kg) determined according to ISO 1133 in the range of 5.0 to 20.0 g / 10 min, more preferably in the range of 6.0 to 15.0 g / 10 min, even more preferably in the range of 6.5 to 12.0 g / 10 min, for example in the range of 7.0 to 10.0 g / 10 min.

[0136] The melting temperature of the propylene copolymer (cPP) is preferably in the range of 120 to 150°C, more preferably in the range of 123 to 145°C, even more preferably in the range of 128 to 140°C, for example in the range of 133 to 139°C.

[0137] The process for the preparation of propylene copolymers (cPP) is preferably a sequential polymerization process comprising at least two reactors connected in series, the process comprising: (A) propylene, and optionally ethylene and C4-C propylene in a first reactor (R-1), which is optionally a slurry reactor (SR), preferably a loop reactor (LR); 12 polymerizing a comonomer selected from an α-olefin, preferably ethylene, to obtain a first propylene copolymer fraction; (B) transferring the first propylene copolymer fraction and unreacted comonomer from the first reactor (R-1) to a second reactor (R-2), which is a gas phase reactor (GPR-1); (C) In the second reactor (R-2), propylene, ethylene and C4 to C 12 providing a comonomer selected from an α-olefin, preferably ethylene; (D) In ​​the second reactor (R-2), in the presence of the first propylene copolymer fraction, and in the presence of ethylene and C4-C 12 polymerizing a comonomer selected from an α-olefin, preferably ethylene, to obtain a second propylene copolymer fraction, said first propylene copolymer fraction and said second propylene copolymer fraction forming a propylene copolymer (cPP) as defined in the present invention; and In the first reactor (R-1) and the second reactor (R-2), polymerization takes place in the presence of a solid catalyst system (SCS).

[0138] This solid catalyst system (SCS) preferably comprises a metallocene catalyst of formula (I) and a cocatalyst as described for the heterophasic polypropylene composition (HECO) according to the first embodiment of the present invention, to which reference is made.

[0139] Therefore, the above mentioned solid catalyst systems (SCS) including all preferred embodiments are preferably applied for the preparation of propylene copolymers (cPP).

[0140] With regard to the term "sequential polymerization process", reference is made to the definition provided above.

[0141] The first reactor (R-1), if applicable, is a slurry reactor (SR) and can be any continuous or simply stirred batch tank reactor or loop reactor operating with a slurry. According to the invention, the slurry reactor (SR) is preferably a loop reactor (LR).

[0142] The second reactor (R-2) and any subsequent reactors are gas phase reactors (GPR). Such gas phase reactors (GPR) can be any mechanically mixed reactor or fluidized bed reactor. Preferably, the gas phase reactors (GPR) comprise mechanically agitated fluidized bed reactors having a gas velocity of at least 0.2 m / sec. It is therefore understood that the gas phase reactors (GPR) are preferably fluidized bed type reactors equipped with mechanical agitators.

[0143] The conditions in each reactor (temperature, pressure, reaction time, monomer feed) depend on the desired product and are within the knowledge of the skilled person. As already indicated above, the first reactor (R-1) is a slurry reactor (SR), e.g., a loop reactor (LR), whereas the second reactor (R-2) is a gas phase reactor (GPR-1). Subsequent reactors, if present, are also gas phase reactors (GPR).

[0144] A preferred multi-stage process is a "loop-gas phase" process such as that developed by Borealis A / S, Denmark (known as BORSTAR® technology) and described in patent literature such as, for example, EP 0 887 379 or WO 92 / 12182.

[0145] Multimodal polymers can be prepared according to several processes, for example those described in WO 92 / 12182, EP 0 887 379 and WO 98 / 58976, the contents of which are incorporated herein by reference.

[0146] With regard to the conditions for the first reactor (R-1), i.e. the slurry reactor (SR), for example the loop reactor (LR), and the second reactor (R-2), i.e. the gas phase reactor (GPR), as well as the residence times, reference is made to the conditions defined above for the heterophasic polypropylene composition (HECO) according to the first embodiment of the invention, which therefore also applies to the optional application of the prepolymerization step.

[0147] The elastomeric ethylene copolymer (E) according to the second embodiment of the present invention is a copolymerizable monomer with ethylene, for example a C3-C 12 It may contain comonomers such as α-olefins, in particular propylene, 1-butene, 1-hexene and / or 1-octene. More specifically, the elastomeric ethylene copolymer (E) according to the second embodiment of the present invention comprises, in addition to ethylene, units derivable from 1-butene, 1-hexene and / or 1-octene.

[0148] It is especially preferred that the elastomeric ethylene copolymer (E) according to the second embodiment of the invention is a copolymer of ethylene and 1-octene.

[0149] Preferably, the elastomeric ethylene copolymer (E) according to the second embodiment of the present invention is a very low density polyethylene, more preferably a very low density polyethylene polymerized using single-site catalysis.

[0150] The elastomeric ethylene copolymer (E) according to the second embodiment of the present invention has a compressibility of 860 to 890 kg / m 3 Preferably, the elastomeric ethylene copolymer (E) according to the second embodiment of the present invention has a density determined according to ISO 1183-187 in the range of 865 to 885 kg / m 3 More preferably, the range is 870 to 884 kg / m 3 In the range of, for example, 879-883 kg / m 3 is in the range.

[0151] Preferably, the elastomeric ethylene copolymer (E) according to the second embodiment of the present invention has a melt flow rate MFR (190°C, 2.16 kg) determined according to ISO 1133 in the range of 0.8 to 20.0 g / 10 min, more preferably in the range of 0.9 to 10.0 g / 10 min, even more preferably in the range of 1.0 to 5.0 g / 10 min, for example in the range of 1.0 to 2.0 g / 10.0 min.

[0152] The ethylene content of the elastomeric ethylene copolymer (E) according to the second embodiment of the present invention is in the range of 55.0 to 85.0 wt.%, preferably in the range of 65.0 to 80.0 wt.%, more preferably in the range of 70.0 to 78.0 wt.%, based on the total weight of the elastomeric ethylene copolymer (E).

[0153] In addition, the elastomeric ethylene copolymer (E) according to the second embodiment of the present invention preferably has a melting temperature Tm, determined according to differential scanning calorimetry (DSC), below 100°C, more preferably in the range of 50°C to 90°C, even more preferably in the range of 55°C to 85°C.

[0154] Alternatively or additionally to the previous paragraph, it is preferred that the elastomeric ethylene copolymer (E) according to the second embodiment of the present invention has a glass transition temperature below -25°C, more preferably in the range of -65°C to -30°C, even more preferably in the range of -60°C to -35°C.

[0155] In one preferred embodiment, the elastomeric ethylene copolymer (E) according to the second embodiment of the present invention is prepared using at least one single-site catalyst. The elastomeric ethylene copolymer (E) according to the second embodiment of the present invention may be prepared using multiple single-site catalysts or may be a blend of multiple elastomeric copolymers prepared using different single-site catalysts. In some embodiments, the elastomeric ethylene copolymer (E) according to the second embodiment of the present invention is a substantially linear ethylene polymer (SLEP). SLEP and other single-site catalyzed elastomeric ethylene copolymers are known in the art, for example, from U.S. Pat. No. 5,272,236. These resins are also commercially available, for example, as Queo™ plastomers available from Borealis, ENGAGE™ plastomer resins available from Dow Chemical Co., EXACT™ polymers available from Exxon, or TAFMER™ polymers available from Mitsui Chemicals, Lucene polymers available from LG, Fortify polymers available from Sabic, or Solumer polymers available from SK Chemicals.

[0156] The heterophasic polypropylene composition (HECO) according to the second embodiment of the present invention may further comprise low density polyethylene (LDPE).

[0157] Preferably, the low density polyethylene (LDPE) has a melt flow rate MFR (190°C, 2.16 kg), determined according to ISO 1133, in the range of 0.5 to 5.0 g / 10 min, more preferably in the range of 0.8 to 10.0 g / 10 min, even more preferably in the range of 1.0 to 7.0 g / 10 min, for example in the range of 2.5 to 3.5 g / 10 min.

[0158] In addition, low density polyethylene (LDPE) has a strength of 900 kg / m 3 More than 920-960 kg / m 3 More preferably, the range is 925 to 955 kg / m 3 It is preferred that the material has a density determined in accordance with ISO 1183-187 in the range of

[0159] Furthermore, the low density polyethylene (LDPE) is preferably a copolymer of ethylene and a polar comonomer copolymerizable with ethylene. Examples of polar comonomers are carboxylic acid vinyl esters selected from the group consisting of vinyl acetate and vinyl pivalate, (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate and hydroxyethyl (meth)acrylate, olefinically unsaturated carboxylic acids such as (meth)acrylic acid, maleic acid and fumaric acid, (meth)acrylic acid derivatives such as (meth)acrylonitrile and (meth)acrylamide, and vinyl ethers such as vinyl methyl ether and vinyl phenyl ether. Preferably, the polar comonomer is a carboxylic acid vinyl ester. It is particularly preferred that the polar comonomer is vinyl acetate.

[0160] Further, the low density polyethylene (LDPE) preferably has a comonomer content, preferably a vinyl acetate content, in the range of 10.0 to 40.0% by weight, more preferably in the range of 15.0 to 35.0% by weight, even more preferably in the range of 20.0 to 33.0% by weight, for example in the range of 25.0 to 30.0% by weight, based on the total weight of the low density polyethylene (LDPE). It is particularly preferred that the low density polyethylene (LDPE) consists only of ethylene units and vinyl acetate units.

[0161] Low density polyethylene (LDPE) is preferably produced by high pressure polymerization involving free radical initiation.

[0162] Preferably, the low density polyethylene (LDPE) is a copolymer known in the art. It is especially preferred that the low density polyethylene (LDPE) is a commercially available copolymer of ethylene and vinyl acetate, OE5328I, from Borealis.

[0163] The heterophasic polypropylene composition (HECO) according to the second embodiment of the present invention is preferably obtained by melt blending a propylene copolymer (cPP), an elastomeric ethylene copolymer (E) and optionally a low density polyethylene (LDPE).

[0164] The fiber reinforced composition (C) according to the second embodiment of the present invention preferably has a melt flow rate MFR2 (230°C, 2.16 kg) determined according to ISO 1133 in the range of 1.0 to 10.0 g / 10 min, more preferably in the range of 1.5 to 6.0 g / 10 min, even more preferably in the range of 2.0 to 4.5 g / 10 min, for example in the range of 2.5 to 3.8 g / 10 min.

[0165] Furthermore, it is preferred that the fiber reinforced composition (C) according to the second embodiment of the present invention has a tensile modulus determined according to ISO 527-1A in the range of 2500 to 5500 MPa, more preferably in the range of 2550 to 4200 MPa, even more preferably in the range of 2600 to 3500 MPa, for example in the range of 2650 to 2800 MPa.

[0166] Additionally or alternatively, the fiber reinforced composition (C) according to the second embodiment of the present invention preferably has an elongation at break determined according to ISO 527-2 of more than 10.0%, more preferably more than 10.3%, even more preferably more than 10.8%, such as 11.0% or more.

[0167] Fiber (F) The essential component of the fiber-reinforced composition (C) is the fiber (F).

[0168] Preferably, the fibers (F) are selected from the group consisting of glass fibers, carbon fibers, polymeric fibers, metal fibers, mineral fibers, ceramic fibers, and mixtures thereof. More preferably, the fibers (F) are glass fibers and / or carbon fibers.

[0169] It is particularly preferred that the fibers (F) are glass fibers (GF). Preferably, the glass fibers (GF) are chopped glass fibers, also known as short glass fibers (SGF) or chopped strands, and / or long glass fibers (LGF), preferably long glass fibers (LGF) obtained from glass rovings.

[0170] It is particularly preferred that the fibers (F) are short glass fibers (GF).

[0171] The chopped glass fibers or short glass fibers (SGF) used in the fiber-reinforced composition (C) preferably have an average length in the range of 2.0 to 10.0 mm, more preferably in the range of 2.3 to 9.0 mm, even more preferably in the range of 2.5 to 8.0 mm, for example in the range of 3.0 to 7.0 mm.

[0172] The chopped glass fibers or short glass fibers (SGF) used in the fiber-reinforced composition (C) preferably have an average diameter of 5 to 20 μm, more preferably 6 to 18 μm, even more preferably 8 to 16 μm.

[0173] Preferably, the short glass fibres (SGF) have an aspect ratio of 125 to 650, preferably 150 to 500, more preferably 200 to 450. The aspect ratio is the relationship between the average length and the average diameter of the fibre.

[0174] Adhesion promoter (AP) According to the invention, the fiber reinforced polypropylene composition (C) may further comprise an adhesion promoter (AP). When the fibers (F) are glass fibers and / or carbon fibers, it is preferred that the fiber reinforced polypropylene composition (C) comprises an adhesion promoter (AP).

[0175] The adhesion promoter (AP) is identified as a polar modified polypropylene (PM-PP) homopolymer or copolymer.

[0176] Polar modified polypropylene (PM-PP) homopolymers or copolymers contain low molecular weight compounds with reactive polar groups. Modified polypropylene homopolymers and copolymers, such as propylene and ethylene or other α-olefins, such as C4-C 10 Copolymers with α-olefins are most preferred since they are highly compatible with the propylene homopolymer or copolymer (PP) of the fiber reinforced polypropylene composition (C) of the present invention.

[0177] In terms of structure, the polar modified polypropylene (PM-PP) homopolymer or copolymer is preferably selected from graft homopolymers or copolymers.

[0178] In this context, polar modified polypropylene (PM-PP) homopolymers or copolymers containing groups derived from polar compounds, in particular polar compounds selected from the group consisting of acid anhydrides, carboxylic acids, carboxylic acid derivatives, primary and secondary amines, hydroxyl compounds, oxazolines and epoxides, as well as ionic compounds, are preferred.

[0179] Specific examples of the polar compounds include unsaturated cyclic anhydrides and their aliphatic diesters and dibasic acid derivatives. In particular, maleic anhydride and maleic acid C1-C 10 Linear and branched dialkyl, C1-C fumarate 10 Linear and branched dialkyl, itaconic anhydride, itaconic acid C1-C 10Compounds selected from linear and branched dialkyl esters, acrylic acid, maleic acid, fumaric acid, itaconic acid and mixtures thereof can be used.

[0180] Particular preference is given to using homopolymers or copolymers of polypropylene grafted with maleic anhydride or acrylic acid as polar modified polypropylene (PM-PP) homopolymers or copolymers, ie adhesion promoters (AP).

[0181] Said modified polymers, i.e. adhesion promoters, can be prepared in a simple manner by reactive extrusion of said polymers with, for example, maleic anhydride or acrylic acid in the presence of a free radical generator, such as an organic peroxide, as disclosed, for example, in U.S. Pat. No. 4,506,056, U.S. Pat. No. 4,753,997 or EP-A-1 805 238.

[0182] The preferred amount of groups derived from polar compounds in the polar modified polypropylene (PM-PP) homopolymer or copolymer, i.e., the adhesion promoter (AP), is 0.5-5.0% by weight. For example, this amount may be in the range of 0.5% to 4.5% by weight, preferably in the range of 0.5% to 4.0% by weight, more preferably in the range of 0.5% to 3.5% by weight.

[0183] For the polar modified polypropylene (PM-PP) homopolymer or copolymer, i.e. for the adhesion promoter (AP), the preferred value of the melt flow rate MFR2(230°C) is at least 20.0-400 g / 10 min. It is particularly preferred that the polar modified polypropylene (PM-PP) homopolymer or copolymer has a melt flow rate MFR2(230°C) in the range of 40.0-300 g / 10 min, more preferably in the range of 50.0-250 g / 10 min.

[0184] In one preferred embodiment of the present invention, the adhesion promoter (AP) is a maleic anhydride modified polypropylene homo / copolymer and / or an acrylic acid modified polypropylene homo / copolymer. Preferably, the adhesion promoter (AP) is a maleic anhydride modified polypropylene homopolymer and / or an acrylic acid modified polypropylene homopolymer, preferably a maleic anhydride modified polypropylene homopolymer. For example, suitable polar modified polypropylene (PM-PP) homopolymers or copolymers include, for example, a polypropylene homopolymer grafted with maleic anhydride (PP-g-MAH) and a polypropylene homopolymer grafted with acrylic acid (PP-g-AA).

[0185] Additives (AD) In addition to the heterophasic polypropylene composition (HECO), the fiber (F) and the adhesion promoter (AP), the fiber reinforced composition (C) of the present invention may contain additives (AD). Typical additives are acid scavengers, antioxidants, colorants, light stabilizers, plasticizers, slip agents, anti-scratch agents, dispersants, processing aids, lubricants, pigments, etc.

[0186] Such additives are commercially available and are described, for example, in "Plastic Additives Handbook" by Hans Zweifel, 6th Edition, 2009 (pp. 1141-1190).

[0187] Furthermore, the term "additive (AD)" according to the invention also comprises carrier materials, in particular polymeric carrier materials.

[0188] Polymeric Support Materials Preferably, the fiber reinforced polypropylene composition (C) of the present invention does not comprise (a) further polymer(s) different from the components of the heterophasic polypropylene composition (HECO) and the adhesion promoter (AP) in an amount of more than 15% by weight, preferably more than 10% by weight, more preferably more than 9% by weight based on the weight of the fiber reinforced polypropylene composition (C). Any polymers which are carrier materials for additives (AD) are counted in the amount of the respective additive and not in the amount of the polymeric compound as indicated in the present invention.

[0189] The polymeric carrier material of the additive (AD) is a carrier polymer to ensure uniform distribution in the fiber reinforced polypropylene composition (C) of the present invention. The polymeric carrier material is not limited to a specific polymer. The polymeric carrier material may be an ethylene homopolymer, an ethylene copolymer obtained from ethylene and an α-olefin comonomer, such as a C3-C8 α-olefin comonomer, a propylene homopolymer, and / or a propylene copolymer obtained from propylene and an α-olefin comonomer, such as ethylene and / or a C4-C8 α-olefin comonomer. It is preferred that the polymeric carrier material does not contain monomer units derivable from styrene or its derivatives.

[0190] Goods The present invention also relates to an article, such as an injection-molded article, comprising the above-defined fiber-reinforced composition (C). The present invention in particular relates to an article, such as an injection-molded article, comprising at least 60% by weight, more preferably at least 80% by weight, even more preferably at least 90% by weight, such as at least 95% by weight or at least 99% by weight, of the above-defined fiber-reinforced polypropylene composition (C). In a particularly preferred embodiment, the present invention relates to an article, such as an injection-molded article, consisting of the above-defined fiber-reinforced composition (C).

[0191] Preferably, the article is an automotive article, such as an injection molded automotive article.

[0192] Further embodiments [1] A fiber-reinforced composition (C), comprising, based on the total weight of the fiber-reinforced composition (C): a) 55.0 to 94.9% by weight, i) a matrix which is a homopolymer or copolymer of propylene (PP) having 1,2 erythro regiodefects in an amount of at least 0.4 mol % and a comonomer content of 8.5 mol % or less; and ii) an elastomeric ethylene copolymer (E) dispersed in the matrix; a heterophasic polypropylene composition (HECO) comprising: b) 5.0 to 45.0% by weight of fiber (F); c) optionally, 0.1 to 5.0 wt. % of an adhesion promoter (AP); Including, The fiber reinforced composition (C) has a melt flow rate MFR2 (230°C, 2.16 kg) determined in accordance with ISO 1133 in the range of 1.0 to 60.0 g / 10 min.

[0193] [2] The heterophasic polypropylene composition (HECO) comprises, based on the total weight of the heterophasic copolymer (HECO), i) the matrix being 60.0 to 95.0% by weight of said propylene homopolymer or copolymer (PP), and ii) 5.0 to 40.0% by weight of the elastomeric ethylene copolymer (E), The fiber-reinforced composition (C) according to embodiment [1],

[0194] [3] The fiber-reinforced composition (C) according to embodiment [1] or embodiment [2], wherein the elastomeric ethylene copolymer (E) has an ethylene content in the range of 15.0 to 85.0 wt.%, based on the total weight of the elastomeric ethylene copolymer (E).

[0195] [4] The fiber-reinforced composition (C) according to any one of embodiments [1] to [3], wherein the heterophasic polypropylene composition (HECO) has a melting temperature Tm, determined according to differential scanning calorimetry (DSC), in the range of 130 to 165 °C.

[0196] [5] The fiber-reinforced composition (C) according to any one of embodiments [1] to [4], wherein the heterophasic polypropylene composition (HECO) has an intrinsic viscosity (IV) measured according to ISO 1628 / 1 (135°C in decalin) of the soluble fraction (SF) determined according to CRYSTEX QC in the range of 1.8 to 3.0 dl / g.

[0197] [6] The fiber (F) is a glass fiber (GF), preferably i) an average length of 2.0 to 10.0 mm, and / or ii) average diameter between 5 and 20 μm The fiber-reinforced composition (C) according to any one of embodiments [1] to [5], wherein the fiber-reinforced composition (C) is short glass fiber (SGF). [7] The fiber-reinforced composition (C) according to any one of embodiments [1] to [6], wherein the adhesion promoter (AP) is a polar-modified polypropylene (PM-PP), which is a homopolymer or copolymer of propylene grafted with maleic anhydride, having a melt flow rate (MFR) (230°C, 2.16 kg) determined in accordance with ISO 1133 of at least 20.0 g / 10 min to 400 g / 10 min.

[0198] [8] i) The propylene homopolymer or copolymer (PP) is a propylene homopolymer (hPP), ii) The elastomeric ethylene polymer (E) is a copolymer of ethylene and propylene. A fiber-reinforced composition (C) according to any one of embodiments [1] to [7].

[0199] [9] The fiber-reinforced composition (C) according to embodiment [8], wherein the propylene homopolymer (hPP) has a melting temperature Tm, determined according to differential scanning calorimetry (DSC), in the range of 140 to 160 °C.

[0200]

[10] The heterophasic polypropylene composition (HECO) is i) a comonomer content in the range of 2.2 to 8.7 mol %, and / or ii) Melt flow rate MFR2 (230°C, 2.16 kg) determined according to ISO 1133 in the range of 20.0 to 100 g / 10 min The fiber-reinforced composition (C) according to embodiment [8] or embodiment [9],

[0201]

[11] The heterophasic polypropylene composition (HECO) is i) a xylene cold solubles (XCS) content, determined at 25°C according to ISO 16152, in the range of 5.0 to 35.0% by weight based on the total weight of said heterophasic polypropylene composition (HECO); and / or ii) the ethylene content of the xylene cold solubles (XCS) fraction in the range of 20.9-44.7 mol % and / or ii) a soluble fraction (SF) determined according to CRYSTEX QC in the range of 5.0 to 35.0 wt. % based on the total weight of said heterophasic polypropylene composition (HECO), and / or iv) Ethylene content of the soluble fraction (SF) determined according to CRYSTEX QC in the range of 20.9-44.7 mol% The fiber-reinforced composition (C) according to any one of embodiments [8] to

[10] ,

[0202]

[12] i) The tensile modulus determined in accordance with ISO 527-1A in the range of 3000 to 6000 MPa, and / or ii) Elongation at break determined according to ISO 527-2 greater than 3.0% The fiber-reinforced composition (C) according to any one of embodiments [8] to

[11] ,

[0203]

[13] i) the propylene homopolymer or copolymer (PP) is a propylene copolymer of propylene and ethylene (cPP) having an ethylene content of 2.2 to 8.5 mol %, ii) The elastomeric ethylene copolymer (E) is a copolymer of ethylene and C4-C ethylene having an ethylene content of 55.0-85.0 wt.% based on the total weight of the elastomeric ethylene copolymer (E). 12 It is a copolymer with an α-olefin, preferably 1-octene. A fiber-reinforced composition (C) according to any one of embodiments [1] to [7].

[0204]

[14] i) the propylene copolymer (cPP) has a melt flow rate MFR2 (230°C, 2.16 kg) determined according to ISO 1133 in the range of 5.0 to 20.0 g / 10 min; and / or ii) The elastomeric ethylene copolymer (E) has a melt flow rate MFR (190°C, 2.16 kg) determined according to ISO 1133 in the range of 0.8 to 20.0 g / 10 min and / or a melt flow rate MFR (190°C, 2.16 kg) determined according to ISO 1133 in the range of 860 to 890 kg / m 3 and / or has a density determined in accordance with ISO 1183-187 in the range iii) The fiber-reinforced composition (C) has a melt flow rate MFR2 (230°C, 2.16 kg) determined according to ISO 1133 in the range of 1.0 to 10.0 g / 10 min. The fiber-reinforced composition (C) according to embodiment

[13] .

[0205]

[15] i) A tensile modulus determined in accordance with ISO 527-1A in the range of 2500 to 5500 MPa, and / or ii) Elongation at break determined according to ISO 527-2 greater than 10.0% The fiber-reinforced composition (C) according to embodiment

[13] or

[14] ,

[0206]

[16] Up to 20.0% by weight, 900 kg / m 3 The fiber-reinforced composition (C) of any one of embodiments [1] to

[15] , further comprising a low-density polyethylene (LDPE) homopolymer or copolymer comprising ethylene and optionally vinyl acetate, having a density determined according to ISO 1183-187 of greater than 100%.

[0207]

[17] The propylene homopolymer or copolymer (PP) is preferably obtained in the presence of a solid catalyst system (SCS) comprising a metallocene complex having the formula (I): [ka] In the above formula (I), each X is independently a σ-donor ligand; L is a divalent bridging group selected from -R'2C-, -R'2C-CR'2-, -R'2Si-, -R'2Si-SiR'2-, -R'2Ge-, and each R' is independently a hydrogen atom or a C1-C aryl group optionally containing one or more heteroatoms or fluorine atoms from groups 14 to 16 of the periodic table. 20 - a hydrocarbyl group, or optionally two R' groups can be taken together to form a ring; Each R 1 can be independently the same or different and are hydrogen, a linear or branched C1-C6 alkyl group, C 7~20 -aryl alkyl, C 7~20 -alkylaryl group or C 6~20 -aryl group or OY group, Y is C 1~10 -hydrocarbyl group, optionally with two adjacent R 1 The groups can be part of a ring that includes the phenyl carbon to which they are attached; Each R 2 can be independently the same or different, and CH-R 8 is a group, R 8 is H or a linear or branched C 1~6 -Alkyl group, C 3~8 -Cycloalkyl group, C 6~10 -aryl group, R 3 is a linear or branched C1-C6 alkyl group, C 7~20 -aryl alkyl, C 7~20 -Alkylaryl group or C6-C 20 -aryl group, R 4 is C(R 9 ) 3 groups, R9 is a linear or branched C1-C6 alkyl group, R 5 is hydrogen or an aliphatic C1-C which may contain one or more heteroatoms from groups 14 to 16 of the periodic table; 20 - a hydrocarbyl group, R 6 is hydrogen or an aliphatic C1-C which may contain one or more heteroatoms from groups 14 to 16 of the periodic table; 20 - a hydrocarbyl group, or R 5 and R 6 together form n groups R 10 wherein n is 0 to 4, Each R 10 are the same or different, C1 to C 20 - a hydrocarbyl group or a C1-C group which may contain one or more heteroatoms belonging to groups 14 to 16 of the periodic table 20 -hydrocarbyl group, R 7 is H or a linear or branched C1-C6-alkyl group or 1-3 groups R 11 is an aryl or heteroaryl group having 6 to 20 carbon atoms, optionally substituted by Each R 11 can be independently the same or different and are hydrogen, a linear or branched C1-C6 alkyl group, C 7~20 -aryl alkyl, C 7~20 -alkylaryl group or C 6~20 -aryl group or OY group, Y is C 1~10 - is a hydrocarbyl group A fiber-reinforced composition (C) according to any one of embodiments [1] to

[16] .

[0208]

[18] An article comprising the fiber-reinforced composition (C) according to any one of embodiments [1] to

[17] .

[0209] The invention will now be described in further detail by the examples provided below. EXAMPLES

[0210] A.Measurement method The following definitions and determination methods of terms apply to the above general description of the invention and the following examples, unless otherwise defined.

[0211] Melt Flow Rate The melt flow rate (MFR) is determined according to ISO 1133 and is given in g / 10 min. MFR is an indicator of the flowability and therefore processability of a polymer. The higher the melt flow rate, the lower the viscosity of the polymer. The MFR2 of polypropylene is determined at a temperature of 230°C or 190°C under a load of 2.16 kg.

[0212] Melting temperature T m and crystallization temperature T c was measured using a Mettler TA820 Differential Scanning Calorimetry (DSC) on 5-7 mg samples. DSC was performed in cycles of heat / cool / heat at a scan rate of 10 °C / min in the temperature range of -30 to +225 °C according to ISO 11357 / Part 3 / Method C2. The crystallization temperature was determined from the cooling step, whereas the melting temperature is determined from the second heating step. All mechanical measurements were performed after a 96 hour conditioning period (23° C., 50% relative humidity) of the specimens.

[0213] 13 Quantification of PP matrix microstructure by C-NMR spectroscopy Quantitative nuclear magnetic resonance (NMR) spectroscopy was used to quantify the tacticity and regioregularity of the polymer crystalline matrix. quantitative 13 C{ 1 The {H} NMR spectrum is 1 H and 13All spectra were recorded in solution using a Bruker Advance III 400 NMR spectrometer operating at 400.15 MHz and 100.62 MHz for C, respectively. 13 A 10 mm extended temperature probe head optimized for C was used and all pressures were recorded using nitrogen gas. For propylene homopolymer, approximately 200 mg of material was dissolved in 1,2-tetrachloroethane-d2 (TCE-d2). To ensure a homogeneous solution, after the initial sample preparation in a heat block, the NMR tube was further heated in a rotating oven for at least 1 h. After insertion into the magnet, the tube was spun at 10 Hz. This setting was chosen mainly due to the high resolution required for the quantification of the tacticity distribution (Busico, V., Cipullo, R., Prog. Polym. Sci. 26 (2001) 443; Busico, V.; Cipullo, R., Monaco, G., Vacatello, M., Segre, AL, Macromolecules 30 (1997) 6251). Standard single-pulse excitation was employed using NOE and bilevel WALTZ16 decoupling schemes (Zhou, Z., Kuemmerle, R., Qiu, X., Redwine, D., Cong, R., Taha, A., Baugh, D.; Winniford, B., J. Mag. Reson. 187 (2007) 225; Busico, V., Carbonniere, P., Cipullo, R., Pellecchia, R., Severn, J., Talarico, G., Macromol. Rapid Commun. 2007, 28, 11289). A total of 8192 (8k) transients were acquired per spectrum. quantitative 13 C{ 1H} NMR spectra were processed and integrated using a proprietary computer program, and relevant quantitative properties were derived from the integrals. For propylene homopolymer, all chemical shifts were internally referenced to the methyl isotactic pentad (mmmm) at 21.85 ppm. Tacticity distribution was quantified by integrating the methyl region from 23.6 to 19.7 ppm, correcting for any sites not related to the conformation of interest (Busico, V., Cipullo, R., Prog. Polym. Sci. 26 (2001) 443; Busico, V., Cipullo, R., Monaco, G., Vacatello, M., Segre, AL, Macromolecules 30 (1997) 6251). Specifically, the effects of regio-defects and comonomers on the quantification of tacticity distribution were corrected by subtracting the integrals of representative regio-defects and comonomers from the specific integral region of the stereosequence. Isotacticity was determined at the pentad level and reported as the percentage of isotactic pentad (mmmm) sequences relative to all pentad sequences. [mmmm]%=100×(mmmm / sum of all pentads) The presence of the 2,1 erythro regiodefect was indicated by the presence of two methyl sites at 17.7 and 17.2 ppm and confirmed by other characteristic sites. No characteristic signals corresponding to other types of regiodefects were observed (Resconi, L., Cavallo, L., Fait, A., Piemontesi, F., Chem. Rev. 2000, 100, 1253). The amount of 2,1-erythro regiodefect was quantified using the average integrals of two characteristic methyl sites at 17.7 and 17.2 ppm. P 21e =(I e6 +I e8 ) / 2 The amount of 1,2 primary insertion propene was quantified based on the methyl region, with correction for sites included in this region but not involved in the primary insertion, and for primary insertion sites excluded from this region. P 12 =I CH3 +P12e The total amount of propene was quantified as the sum of the primary intercalated propene and all other positional defects present. P total =P 12 +P 21e The mole percent of 2,1 erythro regiodefects was quantified relative to total propene. [21e] mol% = 100 × (P 21e / P total )

[0214] Determination of C2 and C3 Content in PP Copolymers Quantitative nuclear magnetic resonance (NMR) spectroscopy was used to quantify the comonomer content and comonomer sequence distribution of the polymers. 13 C{ 1 The H}NMR spectrum 1 H and 13 All spectra were recorded in solution using a Bruker Advance III 400 NMR spectrometer operating at 400.15 MHz and 100.62 MHz for C, respectively. 13A 10 mm extended temperature probe head optimized for 3000 C was used and all air pressures were recorded using nitrogen gas. Approximately 200 mg of material was dissolved in 3 ml of 1,2-tetrachloroethane-d2 (TCE-d2) with chromium(III) acetylacetonate (Cr(acac)3) giving a 65 mM solution of the relaxation agent in the solvent (Singh, G., Kothari, A., Gupta, V., Polymer Testing 28 5 (2009), 475). To ensure a homogenous solution, the NMR tube was further heated in a rotating oven for at least 1 h after the initial sample preparation in a heat block. After insertion into the magnet, the tube was spun at 10 Hz. This setup was chosen mainly due to the high resolution and quantitativeness required for accurate ethylene content quantification. Standard single-pulse excitation without NOE was employed using an optimized tip angle, a recycle delay of 1 s and a bilevel WALTZ16 decoupling scheme (Zhou, Z., Kuemmerle, R., Qiu, X., Redwine, D., Cong, R., Taha, A., Baugh, D.; Winniford, B., J. Mag. Reson. 187 (2007) 225; Busico, V., Carbonniere, P., Cipullo, R., Pellecchia, R., Severn, J., Talarico, G., Macromol. Rapid Commun. 2007, 28, 1128). A total of 6144 (6k) transients were acquired per spectrum.

[0215] quantitative 13 C{ 1H}NMR spectra were processed and integrated using a proprietary computer program, and relevant quantitative properties were derived from the integrals. All chemical shifts were indirectly referenced to the central methylene group of the ethylene block (EEE) at 30.00 ppm using the chemical shift of the solvent. This approach allowed for comparable referencing in the absence of this structural unit. Characteristic signals corresponding to the incorporation of ethylene were observed (Cheng, HN, Macromolecules 17 (1984), 1950).

[0216] The comonomer fraction is 13 C{ 1 The ethylene content was quantified using the method of Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000) 1157) by integration of multiple signals over the entire spectral range of the {H} spectrum. This method was chosen for its robustness and ability to take into account the presence of positional defects, if necessary. The integration region was adjusted slightly to increase applicability over the full range of comonomer contents encountered. For systems where only isolated ethylene in the PPEPP sequence is observed, the method of Wang et al. was modified to reduce the effect of non-zero integrals of sites known to be absent. This approach reduces overestimation of ethylene content for such systems, which reduces the number of sites used to determine absolute ethylene content. E=0.5(Sββ+Sβγ+Sβδ+0.5(Sαβ+Sαγ)) This was achieved by reducing

[0217] With this set of sites, the corresponding integral equation can be written, using the same notation as used in Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157): E = 0.5(I H +I G +0.5(I C +I D )) The equation used for absolute propylene content was not modified. The equation used for absolute propylene content was not modified.

[0218] Comonomer incorporation in mole percent was calculated from the mole fraction. E [mol%] = 100 × fE

[0219] Comonomer incorporation in weight percent was calculated from the mole fraction. E[weight%]=100×(fE×28.06) / ((fE×28.06)+((1-fE)×42.08))

[0220] The comonomer content in the ethylene / 1-octene copolymer is 13 The spectra were measured in a known manner based on Fourier transform infrared spectroscopy (FTIR) using a Nicolet Magna 550 IR spectrometer with Nicolet Omnic FTIR software, calibrated with C-NMR. Films with a thickness of about 250 μm were compression molded from the samples. Similar films were made from calibration samples with known comonomer contents. The comonomer contents were measured using a 1430-1100 cm -1 The absorbance was determined from the spectrum in the wavenumber range of 1410 to 1320 cm. The absorbance is measured as the height of the peak by choosing a so-called short baseline or a long baseline or both. The short baseline is the peak height from about 1410 to 1320 cm through the lowest point. -1 The long baseline is about 1410~1220cm -1 A separate calibration must be performed for each baseline type, and the comonomer content of the unknown samples must be within the range of the comonomer content of the calibration samples.

[0221] The glass transition temperature Tg was determined by dynamic mechanical analysis according to ISO 6721-7. The measurements were performed on compression molded samples (40 × 10 × 1 mm 3 ) was performed in torsional mode at a heating rate of 2°C / min between -100°C and +150°C and a frequency of 1 Hz.

[0222] Density was measured according to ISO 1183-187. Sample preparation is performed by compression molding according to ISO 1872-2:2007.

[0223] Cold xylene soluble part (XCS) The room temperature cold xylene soluble fraction (XCS, wt%) was determined at 25°C according to ISO 16152; 5th edition; 2005-07-01.

[0224] Flexural modulus: Flexural modulus was determined in three-point bending according to ISO 178 on 80 x 10 x 4 mm injection-molded specimens prepared according to ISO 294-1:1996.

[0225] The notched Charpy impact strength was determined at 23° C. according to ISO 179-1 / 1eA by using injection-molded test specimens (80×10×4 mm) prepared according to EN ISO 1873-2.

[0226] Tensile properties were determined on 4 mm thick injection molded dog-bone specimens prepared according to EN ISO 1873-2. Tensile modulus was determined according to ISO 527-1A at a strain rate of 1 mm / min and 23° C., tensile strength and elongation at break (strain) were determined according to ISO 527-2 at a strain rate of 50 mm / min and 23° C.

[0227] Crystex analysis Method using crystalline and soluble parts The crystalline fraction (CF) and soluble fraction (SF) of polypropylene (PP) compositions, as well as the comonomer content and intrinsic viscosity of each fraction, were analyzed by CRYSTEX QC, Polymer Char (Valencia, Spain). A schematic diagram of the CRYSTEX QC instrument is shown in Figure 1a. The crystalline and amorphous fractions are separated by temperature cycling of dissolution at 160°C, crystallization at 40°C and redissolution in 1,2,4-trichlorobenzene (1,2,4-TCB) at 160°C as shown in Figure 1b. Quantification of SF and CF, as well as determination of the ethylene content (C2) of the parent EP copolymer and its soluble and crystalline fractions, is achieved by an infrared detector (IR4) and an on-line two-capillary viscometer used to determine the intrinsic viscosity (iV). The IR4 detector is a multi-wavelength detector that detects IR absorbance in two different bands (CH3 and CH2) to determine the concentration and ethylene content in ethylene-propylene copolymers. The IR4 detector detects ethylene content ( 13 The samples are calibrated using a series of eight EP copolymers with different molecular weights (determined by C-NMR spectroscopy) and with various concentrations ranging from 2 to 13 mg / ml for each used EP copolymer used for calibration. The amounts of soluble (SF) and crystalline (CF) fractions were correlated with the amount of "cold xylene soluble" (XCS) and cold xylene insoluble (XCI) fractions, respectively, by XS calibration and were determined according to standard gravimetric methods according to ISO 16152. The XS calibration is achieved by testing different EP copolymers with XS contents ranging from 2 to 31 wt.%. The intrinsic viscosities (iV) of the parent EP copolymer and its soluble and crystalline fractions are determined using an on-line two-capillary viscometer and correlated with the corresponding iV' determined by standard methods in decalin according to ISO 1628. Calibration is achieved using a range of EPPP copolymers with iV = 2-4 dL / g. A sample of the PP composition to be analyzed is weighed out at a concentration of 10 mg / ml to 20 mg / ml. After automatic filling of the vial with 1,2,4-TCB containing 250 mg / l of 2,6-tert-butyl-4-methylphenol (BHT) as an antioxidant, the sample is dissolved at 160°C with constant stirring at 800 rpm until complete dissolution is achieved, typically for 60 min. As shown in Figures 1a and 1b, a defined volume of sample solution is injected into a column packed with an inert carrier where the crystallization of the sample and the separation of the soluble part from the crystalline part take place. This process is repeated twice. During the first injection, the entire sample is measured at high temperature and the iV [dl / g] and C2 [wt%] of the PP composition are determined. During the second injection, the soluble part (at low temperature) and the crystalline part (at high temperature) are measured in the crystallization cycle (wt% SF, wt% C2, iV). EP means ethylene propylene copolymer. PP means polypropylene.

[0228] Figure 1(a): Schematic of the CRYSTEX QC instrument. Figure 1(b): Elution of an EP copolymer sample and the resulting soluble and crystalline fractions on a TREF column (a column packed with an inert material, e.g., glass beads) (see Del Hierro, P.; Ortin, A.; Monrabal, B.; Soluble Fraction Analysis in polypropylene).

[0229] Intrinsic Viscosity: The intrinsic viscosity (IV) was determined in decalin at 135° C. according to DIN ISO 1628 / 1, October 1999.

[0230] VOC / Fog emissions were measured according to VDA278:2002 on injection molded specimens and granulated formulations. Volatile organic compounds are measured in toluene equivalents / gram. Fogging is measured in hexadecane equivalents / gram. The measurements were carried out with a TDSA supplied by Gerstel using helium 5.0 as carrier gas and a column HP Ultra 2 with a length of 50 m, a diameter of 0.32 mm and a 0.52 μm coating of 5% phenyl-methyl-siloxane. The VOC analysis was performed according to the device settings 1 listed in the above standard with the following main parameters: flow mode splitless, final temperature 90°C; final time 30 min, rate 60 K / min. The cold trap was purged in flow mode split 1:30 with a heating rate of 12 K / s and a final time of 5 min in the temperature range from -150°C to +280°C. The following GC settings were used for the analysis: isothermal at 40°C for 2 min, 3 K / min to 92°C, then 5 K / min to 160°C, then 10 K / min to 280°C, isothermal for 10 min; flow rate 1.3 ml / min. The fog analysis was performed according to the device settings 1 listed in the above standard, with the following main parameters: flow mode splitless, rate 60 K / min; final temperature 120 °C; final time 60 min. The cold trap was purged with a heating rate of 12 K / s in the temperature range from -150 °C to +280 °C, flow mode split 1:30. The following GC settings were used for the analysis: isothermal at 50 °C for 2 min, 25 K / min to 160 °C, then 10 K / min to 280 °C, isothermal for 30 min; flow rate 1.3 ml / min.

[0231] B. Working Example 1. Catalyst synthesis The catalyst used was anti-dimethylsilanediyl[2-methyl-4,8-di(3,5-dimethylphenyl)-1,5,6,7-tetrahydro-s-indacen-1-yl][2-methyl-4-(3,5-dimethylphenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride, disclosed in WO 2020 / 239602 A1 as ICS3.

[0232] Preparation of MAO-silica support A steel reactor equipped with a mechanical stirrer and a filter net was flushed with nitrogen and the reactor temperature was set at 20°C. Silica grade DM-L-303 from AGC Si-Tech Co (5.0 kg), pre-calcined at 600°C, was then added from a feed drum followed by careful pressurization and depressurization with nitrogen using a manual valve. Toluene (22 kg) was then added. The mixture was stirred for 15 minutes. A 30 wt% solution of MAO in toluene from Lanxess (9.0 kg) was then added within 70 minutes via a feed line at the top of the reactor. The reaction mixture was then heated to 90°C and stirred at 90°C for another 2 hours. The slurry was allowed to settle and the mother liquor was filtered off. The catalyst was washed twice with toluene (22 kg) at 90°C followed by settling and filtration. The reactor was cooled to 60°C and the solid was washed with heptane (22.2 kg). Finally, the MAO-treated SiO2 was dried under nitrogen flow at 60° C. for 2 hours with stirring, then under vacuum (−0.5 barg) for 5 hours. The MAO-treated support was collected as a free-flowing white powder. The support was found to contain 12.2 wt. % Al.

[0233] Catalyst preparation 30 wt% MAO in toluene (0.7 kg) was added via a burette at 20°C to a steel nitrogen-blank reactor. Toluene (5.4 kg) was then added with stirring. The catalyst cited above (93 g) was added from a metal cylinder followed by flushing with 1 kg toluene. The mixture was stirred at 20°C for 60 minutes. Trityl tetrakis(pentafluorophenyl)borate (91 g) was then added from a metal cylinder followed by flushing with 1 kg toluene. The mixture was stirred at room temperature for 1 hour. The resulting solution was added over 1 hour to the stirred cake of MAO-silica support prepared as above. The cake was left to stand for 12 hours and then dried under stirring under N2 flow at 60°C for 2 hours and under vacuum (-0.5 barg) for a further 5 hours. The dried catalyst was sampled in the form of a pink free-flowing powder containing 13.9% Al and 0.11% Zr.

[0234] 2. Preparation of heterophasic polypropylene composition (HECO1) and propylene copolymer (cPP) in the reactor In-reactor heterophasic polypropylene compositions (HECO1) and propylene copolymers (cPP) were prepared in the presence of the above catalysts in a sequential process involving a loop reactor and one or two gas-phase reactors. The reaction conditions and the properties of the final polymers are summarized in Tables 1 and 2.

[0235] [Table 1]

[0236] [Table 2]

[0237] 3. Preparation of fiber-reinforced composition (C) containing HECO1 The fiber reinforced composition (C) was obtained by melt blending the in-reactor heterophasic polypropylene composition (HECO1) with glass fiber (GF), adhesion promoter (AP) and additives (AD) in a co-rotating twin screw extruder. The compositions and properties of the inventive and comparative examples are summarized in Table 3.

[0238] [Table 3]

[0239] HECO1a is a commercially available heterophasic propylene copolymer EF015AE from Borealis AG, prepared with a Ziegler-Natta catalyst, having a cold xylene solubles content of 29.0 wt. %, an ethylene content of 11.1 mol. % and an intrinsic viscosity of the xylene solubles of 2.7 dl / g. hP is a melt flow rate MFR2 (230℃) of 75g / 10min, 905kg / m 3 and a glass transition temperature, Tg, of +2° C., prepared using a Ziegler-Natta catalyst. The GF is a commercial product ECS 03 T-480H from Nippon Electric Glass Co., Ltd., with a filament diameter of 10.5 μm and a strand length of 3 mm. AP is adhesion promoter SCONA TPPP 8112 GA by Scona, a maleic anhydride functionalized polypropylene with a maleic anhydride content of 1.4 wt. % and a MFR (190° C., 2.16 kg) of more than 80 g / 10 min. AD1 is a composite of 14.0 wt% tris(2,4-di-t-butylphenyl)phosphite (Kinox-68-G from HPL Additives), 14.0 wt% pentaerythrityl-tetrakis(3-(3',5'-di-tert-butyl-4-hydroxyphenyl)-propionate (Irganox 1010FF from BASF), 36.0 wt% carbon black (50 wt% masterbatch) from Borealis, and 36.0 wt% 905 kg / m 3 and MFR of 3.2 g / 10 min (230° C., 2.16 kg).

[0240] 4. Preparation of compounded heterophasic polypropylene composition (HECO2) Preparation of fiber-reinforced composition (C) containing HECO2 Propylene copolymer (cPP) was melt blended with elastomeric ethylene copolymer (E), glass fiber (GF), adhesion promoter (AP), and optionally low density polyethylene (LDPE) and additives (AD) in a co-rotating twin screw extruder. The compositions and properties of the inventive and comparative examples are summarized in Table 4.

[0241] [Table 4]

[0242] cPPa is a commercially available propylene ethylene random copolymer RD208CF from Borealis AG, prepared with a Ziegler-Natta catalyst, having an ethylene content of 7.3 mol%, a melt flow rate MFR2 determined according to ISO 1133 of 8.0 g / 10 min (230° C., 2.16 kg) and a melting temperature Tm of 140° C. cPPb is a metallocene propylene ethylene random copolymer according to example IE1 of WO 2015 / 121160 A1 with an ethylene content of 4.1 mol% and a melt flow rate MFR2 (230° C., 2.16 kg) determined according to ISO 1133 of 4.0 g / 10 min. E is the melt flow rate (190°C, 2.16 kg) determined according to ISO 1133 of 1.1 g / 10 min, the melting temperature Tm of 72°C, the glass transition temperature Tg of -52°C, and the glass transition temperature Tg of 882 kg / m 3 and an ethylene content of 75.5 wt. %, commercially available Queo 8201 of ethylene and 1-octene from Borealis AG. LDPE has a melt flow rate (190°C, 2.16 kg) determined in accordance with ISO 1133 of 3.0 g / 10 min, 950 kg / m 3 and a vinyl acetate content of 28.0 wt. %, commercially available ethylene and vinyl acetate copolymer OE5328 from Borealis AG. AD2 was made from 20.0 wt% erucamide (Finawax-E by Fine Organics), 6.6 wt% tris(2,4-di-tert-butylphenyl)phosphite (Irgafox 168 by BASF), 6.6 wt% pentaerythrityl-tetrakis(3-(3',5'-di-tert-butyl-4-hydroxyphenyl)-propionate (Irganox 1010FF by BASF), 33.3 wt% carbon black (50 wt% masterbatch) by Borealis, and 33.3 wt% 905 kg / m2 of 100% ethylcellulose. 3and MFR of 3.2 g / 10 min (230° C., 2.16 kg). AD3 is a masterbatch consisting of 18.18 wt.% tris(2,4-di-tert-butylphenyl)phosphite (Irgafox 168 by BASF), 36.36 wt.% pentaerythrityl-tetrakis(3-(3',5'-di-tert-butyl-4-hydroxyphenyl)-propionate (Irganox 1010FF by BASF) and 45.45 wt.% distearyl-thio-propionate (Irganox PS-802 FL by BASF).

Claims

1. A fiber-reinforced composition (C), based on the total weight of the fiber-reinforced composition (C): a) 55.0-94.9 wt. % of a heterophasic polypropylene composition (HECO), having a melt flow rate MFR 2 (230° C., 2.16 kg) determined according to ISO 1133 in the range of 20.0 to 100 g / 10 min; i) a matrix which is a propylene homopolymer (hPP) having 1,2 erythro regiodefects in an amount of at least 0.4 mol %; and ii) an elastomeric ethylene copolymer (E) dispersed in said matrix; a heterophasic polypropylene composition (HECO) comprising b) 5.0 to 45.0% by weight of fibers (F); c) optionally, 0.1 to 5.0 wt. % of an adhesion promoter (AP); Including, The fiber-reinforced composition (C) has a melt flow rate MFR determined according to ISO 1133 in the range of 10.0 to 60.0 g / 10 min. 2 (230°C, 2.16 kg).

2. The heterophasic polypropylene composition (HECO) comprises, based on the total weight of the heterophasic copolymer (HECO), i) the matrix being 60.0-95.0% by weight of the propylene homopolymer (hPP); and ii) 5.0 to 40.0 wt. % of said elastomeric ethylene copolymer (E); The fiber-reinforced composition (C) according to claim 1 .

3. The fiber reinforced composition (C) according to claim 1 or claim 2, wherein the elastomeric ethylene copolymer (E) has an ethylene content in the range of 15.0 to 85.0 wt.%, based on the total weight of the elastomeric ethylene copolymer (E).

4. The fiber reinforced composition (C) according to any one of claims 1 to 3, wherein the heterophasic polypropylene composition (HECO) has a melting temperature Tm, determined according to Differential Scanning Calorimetry (DSC), in the range of 130 to 165°C.

5. 5. The fiber reinforced composition (C) according to any one of claims 1 to 4, wherein the heterophasic polypropylene composition (HECO) has an intrinsic viscosity (IV) measured according to ISO 1628 / 1 (135°C in decalin) of the soluble fraction (SF) determined according to CRYSTEX QC in the range of 1.8 to 3.0 dl / g.

6. The fiber-reinforced composition (C) according to any one of claims 1 to 5, wherein the fiber (F) is a glass fiber (GF).

7. The fiber (F) i) an average length of 2.0 to 10.0 mm; and / or ii) average diameter between 5 and 20 μm The fiber-reinforced composition (C) according to any one of claims 1 to 6, which is short glass fiber (SGF) having the following formula:

8. The fiber reinforced composition (C) according to any one of claims 1 to 7, wherein the adhesion promoter (AP) is a polar modified polypropylene (PM-PP) which is a homopolymer or copolymer of propylene grafted with maleic anhydride having a melt flow rate MFR (230°C, 2.16 kg) determined according to ISO 1133 of at least 20.0 g / 10 min to 400 g / 10 min.

9. A fiber-reinforced composition (C) described in any one of claims 1 to 8, wherein the elastomeric ethylene polymer (E) is a copolymer of ethylene and propylene.

10. The fiber reinforced composition (C) according to claim 1, wherein the propylene homopolymer (hPP) has a melting temperature Tm determined according to differential scanning calorimetry (DSC) in the range of 140-160°C.

11. The fiber reinforced composition (C) according to claim 9 or claim 10, wherein said heterophasic polypropylene composition (HECO) has a comonomer content in the range of 2.2 to 8.7 mol %.

12. The heterophasic polypropylene composition (HECO) has one or both of the following properties i) and ii) according to any one of claims 9 to 11. i) a xylene cold solubles (XCS) content, determined at 25°C according to ISO 16152, ranging from 5.0 to 35.0 wt.% based on the total weight of said heterophasic polypropylene composition (HECO); ii) a soluble fraction (SF) determined according to CRYSTEX QC in the range of 5.0 to 35.0 wt.% based on the total weight of said heterophasic polypropylene composition (HECO);

13. The heterophasic polypropylene composition (HECO) has one or both of the following properties i) and ii) according to any one of claims 9 to 12. i) the ethylene content of the xylene cold solubles (XCS) fraction in the range of 20.9 to 44.7 mole percent ii) ethylene content of the soluble fraction (SF) determined according to CRYSTEX QC in the range of 20.9 to 44.7 mol %.

14. A fiber-reinforced composition (C) described in any one of claims 9 to 13, having one or both of the following characteristics i) and ii). i) Tensile modulus determined according to ISO 527-1A in the range of 3000 to 6000 MPa ii) Elongation at break determined according to ISO 527-2 of greater than 3.0%

15. The fiber-reinforced composition (C) according to any one of claims 1 to 14, wherein the propylene homopolymer (hPP) is obtained in the presence of a solid catalyst system (SCS) comprising a metallocene complex.

16. The propylene homopolymer (hPP) is obtained in the presence of a solid catalyst system (SCS) comprising a metallocene complex having the formula (I): 【Chemistry 1】 In the formula (I), each X is independently a σ-donor ligand; L is a divalent bridging group selected from -R' 2 C-, -R' 2 C-CR' 2 -, -R' 2 Si-, -R' 2 Si-SiR' 2 -, -R' 2 Ge-, where each R' is independently a hydrogen atom or a C 1 -C 20 -hydrocarbyl group which may contain one or more heteroatoms from groups 14 to 16 of the periodic table or fluorine atoms, or optionally two R' groups can be joined together to form a ring; each R 1 independently may be the same or different and is hydrogen, a linear or branched C 1 -C 6 -alkyl group, a C 7-20 -arylalkyl, a C 7-20 -alkylaryl group or a C 6-20 -aryl group or an OY group, where Y is a C 1-10 -hydrocarbyl group, and optionally two adjacent R 1 groups may be part of a ring that includes the phenyl carbon to which they are attached; each R 2 can be independently the same or different and is a CH 2 -R 8 group, where R 8 is H or a linear or branched C 1-6 -alkyl group, a C 3-8 -cycloalkyl group, a C 6-10 -aryl group; R 3 is a linear or branched C 1 -C 6 -alkyl group, a C 7-20 -arylalkyl, a C 7-20 -alkylaryl group or a C 6 -C 20 -aryl group; R 4 is a C(R 9 ) 3 group, R 9 being a linear or branched C 1 -C 6 -alkyl group; R 5 is hydrogen or an aliphatic C 1 -C 20 -hydrocarbyl group which may contain one or more heteroatoms from Groups 14 to 16 of the Periodic Table; R 6 is hydrogen or an aliphatic C 1 -C 20 -hydrocarbyl group which may contain one or more heteroatoms from groups 14 to 16 of the periodic table; or R 5 and R 6 together may form a 5-membered saturated carbocyclic ring optionally substituted by n groups R 10 , n being 0 to 4; each R 10 may be the same or different and may be a C 1 -C 20 -hydrocarbyl group or a C 1 -C 20 -hydrocarbyl group optionally containing one or more heteroatoms belonging to groups 14 to 16 of the periodic table; R 7 is H or a linear or branched C 1 -C 6 -alkyl group or an aryl or heteroaryl group having 6 to 20 carbon atoms, which may be substituted by 1 to 3 radicals R 11 ; A fiber-reinforced composition (C) according to any one of claims 1 to 15, wherein each R 11 can be independently the same or different and is hydrogen, a linear or branched C 1 -C 6 -alkyl group, a C 7-20 -arylalkyl, a C 7-20 -alkylaryl group or a C 6-20 -aryl group or an OY group, where Y is a C 1-10 -hydrocarbyl group.

17. 17. An article comprising a fiber-reinforced composition (C) according to any one of claims 1 to 16.

Citation Information

Patent Citations

  • Propylene copolymer composition with good low temperature impact toughness and high transparency

    JP2005529227A

  • Flexible propylene copolymer composition with high transparency

    JP2005533138A

  • Thermoplastic elastomer composition

    JP2018193532A

  • Foamed polypropylene composition

    JP2020513423A

  • Polyolefin composition with reduced odor and haze

    JP2020521026A